Surface Protection Film

The surface protective film addresses the challenge of thickened adhesive layers with light peelability and low haze by using a urethane-based pressure-sensitive adhesive composition with specific additives, ensuring effective protection and inspection for components with large steps.

JP7648376B2Active Publication Date: 2025-03-18NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020211370
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-21
Publication Date
2025-03-18
Estimated Expiration
2040-12-21

AI Technical Summary

Technical Problem

Existing surface protective films for optical and electronic components face challenges in achieving thickened adhesive layers with light peelability and low haze, particularly when attached to components with large steps like organic EL displays.

Method used

A surface protective film with a urethane adhesive layer composed of a urethane-based pressure-sensitive adhesive composition, including a urethane prepolymer, a polyol with a specific molecular weight range, and a polyfunctional isocyanate compound, optimized with an ionic compound and a fluorine-based or silicone-based additive to enhance compatibility and reduce haze.

Benefits of technology

The solution enables the surface protective film to achieve thickened adhesive layers that maintain light peelability and low haze, effectively protecting components with large steps and ensuring excellent inspection properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648376000007
    Figure 0007648376000007
  • Figure 0007648376000001
    Figure 0007648376000001
  • Figure 0007648376000002
    Figure 0007648376000002
Patent Text Reader

Abstract

To provide a surface protective film capable of thickening an adhesive layer while exhibiting easy detachability and realizing a low haze, and also to provide an optical member and an electronic member with such a surface protective film adhered.SOLUTION: A surface protective film includes an urethane-based adhesive layer. The urethane-based adhesive layer is composed of an urethane-based tackiness agent formed of an urethane-based adhesive composition. The urethane-based adhesive composition contains an urethane prepolymer P, a polyol A, and a polyfunctional isocyanate compound B. A weight ratio of the P and the A is P:A=(50 to 99):(1 to 50). The polyol A contains: a first polyol A1 having a number average molecular weight mn of 5000 to 20000; and a second polyol A2 having a number average molecular weight mn of 300 to 4999. A weight ratio of the A1 and the A2 is 1.0≤(A1 / A2)≤3.5.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a surface protection film. [Background technology]

[0002] Surface protection films are attached to optical and electronic components to prevent their surfaces from being scratched during processing, assembly, inspection, transportation, etc. Such surface protection films are peeled off from the optical and electronic components when surface protection is no longer necessary (Patent Document 1).

[0003] When attempting to peel off such a surface protection film from an optical or electronic component to which such a surface protection film is attached, it is important that the film can be peeled off smoothly only at the interface between the surface protection film and the optical or electronic component. Furthermore, when protecting a display with a large step, such as an organic EL display, a thick pressure-sensitive adhesive layer is required so that it can conform to the step.

[0004] As the pressure-sensitive adhesive layer provided in a surface protection film, a pressure-sensitive adhesive layer composed of various pressure-sensitive adhesives is known. In terms of excellent reworkability, wettability, and transparency, a urethane-based pressure-sensitive adhesive layer composed of a urethane-based pressure-sensitive adhesive is preferably used as the pressure-sensitive adhesive layer provided in a surface protection film to be attached to an optical component or an electronic component.

[0005] There are two methods for producing urethane-based adhesives: the one-shot method, in which a urethane adhesive is produced by directly reacting a polyol with a polyfunctional isocyanate without using a urethane prepolymer, and the prepolymer method, in which a urethane adhesive is produced by reacting a urethane prepolymer with a polyfunctional isocyanate.

[0006] The one-shot method uses a polyol with a number-average molecular weight of around 10,000, which is directly cured by reaction with a polyfunctional isocyanate, resulting in a high crosslink density and ensuring easy releasability. On the other hand, the one-shot method is not suitable for thick film formation because the viscosity of the adhesive solution is low (Patent Document 2).

[0007] The prepolymer method is suitable for thick film formation because the viscosity of the adhesive solution is high. On the other hand, the prepolymer method makes it difficult to ensure easy releasability because the crosslink density of the adhesive obtained by curing through a reaction with a polyfunctional isocyanate is low. For this reason, a technology has been reported that ensures easy releasability by using a polyol with a number-average molecular weight of 300 or less in combination (Patent Document 3).

[0008] However, when a urethane prepolymer is used in combination with a polyol having a number-average molecular weight of 300 or less, the molecular weights of the two materials differ significantly, resulting in poor compatibility and a problem of an increased haze value for the adhesive. An increased haze value for the adhesive not only leads to a decrease in the quality of the surface protection film, but also leads to a decrease in inspectability for surface protection films that are bonded to optical or electronic components, for example. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Laid-Open No. 2016-17109 [Patent Document 2] Patent No. 5501489 [Patent Document 3] Japanese Patent Application Publication No. 2018-62595 Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a surface protection film that allows for a thick pressure-sensitive adhesive layer, exhibits easy peelability, and achieves low haze, and also to provide optical and electronic components to which such a surface protection film is attached. [Means for solving the problem]

[0011] The surface protective film according to an embodiment of the present invention comprises: A surface protection film including a urethane-based pressure-sensitive adhesive layer, the urethane-based pressure-sensitive adhesive layer is composed of a urethane-based pressure-sensitive adhesive formed from a urethane-based pressure-sensitive adhesive composition, The urethane-based pressure-sensitive adhesive composition contains a urethane prepolymer P, a polyol A, and a polyfunctional isocyanate compound B, the weight ratio of the urethane prepolymer P to the polyol A is P:A=(50 to 99):(1 to 50), The polyol A includes a first polyol A1 having a number average molecular weight Mn of 5,000 to 20,000 and a second polyol A2 having a number average molecular weight Mn of 300 to 4,999, The weight ratio of the first polyol A1 to the second polyol A2 is 1.0≦(A1 / A2)≦3.5.

[0012] In one embodiment, the urethane-based pressure-sensitive adhesive composition contains an ionic compound, and the content of the ionic compound relative to the total amount of the urethane prepolymer P and the polyol A is 0.05% by weight or more.

[0013] In one embodiment, the urethane-based pressure-sensitive adhesive composition contains at least one selected from the group consisting of a fluorine-based additive and a silicone-based additive, and the content ratio of the total amount of the fluorine-based additive and the silicone-based additive to the total amount of the urethane prepolymer P and the polyol A is 0.01 wt % or more.

[0014] In one embodiment, the weight ratio of the first polyol A1 to the second polyol A2 satisfies 1.0≦(A1 / A2)≦2.0.

[0015] In one embodiment, the urethane-based pressure-sensitive adhesive layer is attached to a glass plate, and after 30 minutes at 23°C, the peel strength when peeled from the glass plate at a peel angle of 180° and a peel speed of 300 mm / min is 0.5 gf / 25 mm to 2.0 gf / 25 mm.

[0016] In one embodiment, the urethane-based pressure-sensitive adhesive layer is attached to a glass plate, and after 24 hours at 23°C, the layer is peeled from the glass plate at a peel angle of 180° and a peel speed of 0.3 m / min, and the residual adhesion rate to the glass plate is 80% or more.

[0017] The optical member according to the embodiment of the present invention has a surface protection film according to the embodiment of the present invention attached thereto.

[0018] The electronic component according to the embodiment of the present invention has a surface protection film according to the embodiment of the present invention attached thereto. [Effects of the Invention]

[0019] According to the present invention, it is possible to provide a surface protection film that can have a thick pressure-sensitive adhesive layer, exhibit easy peelability, and achieve low haze, and it is also possible to provide optical components and electronic components to which such a surface protection film is attached. [Brief explanation of the drawings]

[0020] [Figure 1] 1 is a schematic cross-sectional view of a surface protection film according to a preferred embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0021] ≪≪1. Surface protection film≫≫ The surface protection film according to the embodiment of the present invention includes a urethane-based pressure-sensitive adhesive layer, and any appropriate release liner having releasability may be attached to the adhesive surface side of the urethane-based pressure-sensitive adhesive layer, as long as the effects of the present invention are not impaired.

[0022] The surface protection film according to the embodiment of the present invention preferably has a substrate layer and a urethane-based pressure-sensitive adhesive layer. The substrate layer may be a single layer or two or more layers. The urethane-based pressure-sensitive adhesive layer may be a single layer or two or more layers. In addition to the substrate layer and the urethane-based pressure-sensitive adhesive layer, the surface protection film of the present invention may have any other appropriate layer as long as the effects of the present invention are not impaired.

[0023] 1 is a schematic cross-sectional view of a surface protection film according to a preferred embodiment of the present invention. The surface protection film 10 comprises a substrate layer 1 and a pressure-sensitive adhesive layer 2. The surface protection film of the present invention may further comprise any other appropriate layers, such as a release liner, as necessary (not shown).

[0024] The surface of the base layer 1 on which the adhesive layer 2 is not applied may be subjected to a release treatment, for example, by adding a fatty acid amide, polyethyleneimine, a long-chain alkyl additive, or the like to the base layer, in order to form a roll that is easy to unwind, or a coating layer made of any suitable release agent, such as a silicone-based, long-chain alkyl-based, or fluorine-based release agent, may be provided.

[0025] Examples of release liners that can be provided on the adhesive surface side of the urethane-based pressure-sensitive adhesive layer include release liners in which the surface of a substrate (liner substrate) such as paper or plastic film is silicone-treated, and release liners in which the surface of a substrate (liner substrate) such as paper or plastic film is laminated with a polyolefin-based resin.

[0026] Examples of plastic films that can be used as the substrate of the release liner include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.

[0027] The thickness of the release liner is preferably 1 μm to 500 μm, more preferably 3 μm to 450 μm, even more preferably 5 μm to 400 μm, and particularly preferably 10 μm to 300 μm.

[0028] The thickness of the surface protection film according to the embodiment of the present invention can be set to any appropriate thickness depending on the application, and is typically preferably 10 μm to 300 μm, more preferably 15 μm to 250 μm, even more preferably 20 μm to 200 μm, and particularly preferably 25 μm to 150 μm.

[0029] In the surface protection film according to the embodiment of the present invention, the urethane-based pressure-sensitive adhesive layer can be made thick. Accordingly, the thickness of the urethane-based pressure-sensitive adhesive layer included in the surface protection film of the present invention is preferably 1 μm to 150 μm, more preferably 5 μm to 150 μm, even more preferably 10 μm to 150 μm, even more preferably 20 μm to 150 μm, even more preferably 30 μm to 150 μm, even more preferably 40 μm to 150 μm, even more preferably 50 μm to 150 μm, particularly preferably 60 μm to 150 μm, and most preferably 65 μm to 150 μm. Since the urethane-based pressure-sensitive adhesive layer can be made thick in this way, the surface protection film according to the embodiment of the present invention can effectively conform to the unevenness when protecting a display with a large unevenness, such as an organic EL display.

[0030] The surface protection film according to an embodiment of the present invention can exhibit easy releasability. When the urethane pressure-sensitive adhesive layer contained in the surface protection film is attached to a glass plate and, after 30 minutes at 23°C, peeled from the glass plate at a peel angle of 180° and a peel rate of 300 mm / min, the peel force is preferably 0.5 gf / 25 mm to 5.0 gf / 25 mm, more preferably 0.5 gf / 25 mm to 4.0 gf / 25 mm, even more preferably 0.5 gf / 25 mm to 3.0 gf / 25 mm, particularly preferably 0.5 gf / 25 mm to 2.5 gf / 25 mm, and most preferably 0.5 gf / 25 mm to 2.0 gf / 25 mm. When the peel force is within the above range, the surface protection film according to an embodiment of the present invention can exhibit excellent easy releasability.

[0031] The surface protection film according to the embodiment of the present invention can achieve low haze. In the surface protection film of the present invention, the haze of the urethane-based pressure-sensitive adhesive layer contained therein is preferably 4.5% or less, more preferably 4.0% or less, even more preferably 3.5% or less, particularly preferably 3.0% or less, and most preferably 2.5% or less. When the haze is within the above range, the surface protection film according to the embodiment of the present invention can achieve excellent low haze and can exhibit, for example, excellent inspectability.

[0032] The surface protection film according to the embodiment of the present invention has a residual adhesion rate to the glass plate after laminating the urethane-based pressure-sensitive adhesive layer contained therein to a glass plate, and then peeling it from the glass plate at a peel angle of 180° and a peel speed of 0.3 m / min at 23° C. for 24 hours. The residual adhesion rate to the glass plate is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, particularly preferably 85% or more, and most preferably 90% or more. If the residual adhesion rate is within the above range, the surface protection film according to the embodiment of the present invention can reduce adhesive residue.

[0033] The surface protection film according to an embodiment of the present invention has a peel electrification voltage of preferably 15 kV or less, more preferably 10 kV or less, even more preferably 5 kV or less, particularly preferably 2 kV or less, and most preferably 1 kV or less when the urethane pressure-sensitive adhesive layer contained therein is attached to a glass plate and then peeled from the glass plate at a peel angle of 150° and a peel speed of 30 m / min at 23° C. If the peel electrification voltage is within the above range, the surface protection film according to an embodiment of the present invention can effectively prevent charging during peeling.

[0034] ≪1-1. Urethane adhesive layer≫ The urethane-based pressure-sensitive adhesive layer is composed of a urethane-based pressure-sensitive adhesive. The urethane-based pressure-sensitive adhesive is formed from a urethane-based pressure-sensitive adhesive composition. That is, the urethane-based pressure-sensitive adhesive formed from the urethane-based pressure-sensitive adhesive composition forms a layer shape, thereby becoming a pressure-sensitive adhesive layer.

[0035] A urethane-based pressure-sensitive adhesive can be defined as something formed from a urethane-based pressure-sensitive adhesive composition. This is because a urethane-based pressure-sensitive adhesive becomes a urethane-based pressure-sensitive adhesive when the urethane-based pressure-sensitive adhesive composition undergoes a crosslinking reaction due to heating or ultraviolet irradiation, etc., and therefore it is impossible and impractical to directly identify a urethane-based pressure-sensitive adhesive by its structure ("impossible / impractical circumstances"). Therefore, the definition of "something formed from a urethane-based pressure-sensitive adhesive composition" appropriately identifies a urethane-based pressure-sensitive adhesive as a "product."

[0036] As described above, in the surface protection film of the present invention, the urethane-based pressure-sensitive adhesive layer can be thickened, so the thickness of the urethane-based pressure-sensitive adhesive layer is preferably 1 μm to 150 μm, more preferably 5 μm to 150 μm, even more preferably 10 μm to 150 μm, even more preferably 20 μm to 150 μm, even more preferably 30 μm to 150 μm, even more preferably 40 μm to 150 μm, even more preferably 50 μm to 150 μm, particularly preferably 60 μm to 150 μm, and most preferably 65 μm to 150 μm. If the urethane-based pressure-sensitive adhesive layer can be thickened in this way, the surface protection film according to the embodiment of the present invention can well conform to the unevenness when protecting a display with a large unevenness, such as an organic EL display.

[0037] The urethane-based pressure-sensitive adhesive is formed from a urethane-based pressure-sensitive adhesive composition. Any appropriate formation method can be used as long as it does not impair the effects of the present invention. Examples of such formation methods include a method (direct method) in which the urethane-based pressure-sensitive adhesive composition is directly applied to any appropriate substrate film (e.g., the substrate layer in a surface protection film according to an embodiment of the present invention) and dried or cured, and a method (transfer method) in which the urethane-based pressure-sensitive adhesive composition is applied to the surface (release surface) of a release liner and dried or cured to form a urethane-based pressure-sensitive adhesive layer on the surface, and the urethane-based pressure-sensitive adhesive layer is then bonded to a substrate film (e.g., the substrate layer in a surface protection film according to an embodiment of the present invention) to transfer the urethane-based pressure-sensitive adhesive layer. From the viewpoint of the anchoring properties of the pressure-sensitive adhesive layer, the direct method is typically preferably used.

[0038] As a method for providing (typically applying) such a urethane-based pressure-sensitive adhesive layer, various conventionally known methods can be appropriately adopted, such as roll coating, gravure coating, reverse coating, kiss coating, dip roll coating, bar coating, roll brushing, spray coating, knife coating, air knife coating, spray coating, comma coating, direct coating, and coating with a die coater.

[0039] The urethane pressure-sensitive adhesive composition can be dried under heating (for example, by heating to about 60° C. to 150° C.) as needed. The urethane pressure-sensitive adhesive composition can be cured by, for example, ultraviolet light, laser radiation, α-rays, β-rays, γ-rays, X-rays, or electron beams.

[0040] The urethane-based pressure-sensitive adhesive composition contains a urethane prepolymer P, a polyol A, and a polyfunctional isocyanate compound B.

[0041] The weight ratio of the total amount of urethane prepolymer P, polyol A, and polyfunctional isocyanate compound B in the urethane-based pressure-sensitive adhesive composition is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, particularly preferably 95% by weight to 100% by weight, and most preferably 98% by weight to 100% by weight. By adjusting the weight ratio of the total amount of urethane prepolymer P and polyol A in the urethane-based pressure-sensitive adhesive composition within the above range, the surface protection film of the present invention can effectively exhibit the effects of the present invention.

[0042] The weight ratio of urethane prepolymer P to polyol A in the urethane pressure-sensitive adhesive composition is preferably P:A = (50-99):(1-50), more preferably (50-90):(10-50), even more preferably (50-80):(20-50), and particularly preferably (50-70):(30-50). By adjusting the weight ratio of urethane prepolymer P to polyol A in the urethane pressure-sensitive adhesive composition within the above range, the surface protection film of the present invention can effectively exhibit the effects of the present invention.

[0043] The equivalent ratio of NCO groups to OH groups, expressed as NCO groups / OH groups, in the urethane prepolymer P and the polyfunctional isocyanate compound B is preferably 1.0 to 2.0, more preferably 1.1 to 1.9, even more preferably 1.2 to 1.8, and particularly preferably 1.2 to 1.7. By adjusting the equivalent ratio of NCO groups / OH groups within the above range, the surface protection film according to the embodiment of the present invention has excellent wettability and conformability to unevenness, even when attached to an adherend with large surface irregularities, thereby achieving a sufficiently high adhesion rate.

[0044] The content of the polyfunctional isocyanate compound B in the urethane-based pressure-sensitive adhesive composition is preferably 2.5 to 40 parts by weight, more preferably 4 to 30 parts by weight, even more preferably 5 to 20 parts by weight, and particularly preferably 6 to 15 parts by weight, relative to 100 parts by weight of the urethane prepolymer P. By adjusting the content of the polyfunctional isocyanate compound B within the above range, the surface protection film according to the embodiment of the present invention has excellent wettability and excellent conformability to uneven surfaces, even when attached to an adherend with large surface irregularities, thereby achieving a sufficiently high adhesion rate.

[0045] In the present invention, the urethane-based pressure-sensitive adhesive constituting the urethane-based pressure-sensitive adhesive layer is not a urethane-based pressure-sensitive adhesive produced by the one-shot method in which a urethane pressure-sensitive adhesive is produced by directly reacting a polyol with a polyfunctional isocyanate without using a urethane prepolymer, but a urethane-based pressure-sensitive adhesive produced by the prepolymer method in which a urethane pressure-sensitive adhesive is produced by reacting a urethane prepolymer P with a polyfunctional isocyanate compound B. Because the surface protection film of the present invention has a urethane-based pressure-sensitive adhesive layer composed of a urethane-based pressure-sensitive adhesive produced by the prepolymer method in this way, the urethane-based pressure-sensitive adhesive layer can be made thick, and can conform well to the steps when protecting a display with large steps, such as an organic EL display.

[0046] <1-1-1. Urethane prepolymer P> The urethane prepolymer P is typically a polyurethane polyol, and is preferably obtained by reacting a polyester polyol (p1) and a polyether polyol (p2) with an organic polyisocyanate compound (p3) in the presence or absence of a catalyst. Commercially available urethane prepolymers may be used as the urethane prepolymer P.

[0047] The urethane prepolymer P may be of only one type, or of two or more types.

[0048] The number average molecular weight Mn of the urethane prepolymer P is preferably 1,000 to 100,000.

[0049] Any suitable polyester polyol can be used as the polyester polyol (p1) as long as it does not impair the effects of the present invention. Examples of such polyester polyols (p1) include polyester polyols obtained by reacting an acid component with a glycol component. Examples of acid components include terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, and trimellitic acid. Examples of glycol components include ethylene glycol, propylene glycol, diethylene glycol, butylene glycol, 1,6-hexane glycol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,4-butanediol, neopentyl glycol, and butylethylpentanediol. Examples of polyol components include glycerin, trimethylolpropane, and pentaerythritol. In addition to these, examples of the polyester polyol (p1) include polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, poly(β-methyl-γ-valerolactone), and polyvalerolactone.

[0050] The molecular weight of the polyester polyol (p1) can range from low to high. The molecular weight of the polyester polyol (p1) is preferably a number average molecular weight of 500 to 5,000. If the number average molecular weight is less than 500, the reactivity may be high and gelation may occur easily. If the number average molecular weight exceeds 5,000, the reactivity may be low and the cohesive force of the polyurethane polyol itself may be reduced. The amount of polyester polyol (p1) used is preferably 10 mol % to 90 mol % of the polyol constituting the urethane prepolymer P (typically, polyurethane polyol).

[0051] As the polyether polyol (p2), any suitable polyether polyol can be used as long as it does not impair the effects of the present invention. Examples of such polyether polyols (p2) include polyether polyols obtained by polymerizing oxirane compounds such as ethylene oxide, propylene oxide, butylene oxide, and tetrahydrofuran using a low-molecular-weight polyol such as water, propylene glycol, ethylene glycol, glycerin, or trimethylolpropane as an initiator. Examples of such polyether polyols (p2) include polyether polyols having two or more functional groups, such as polypropylene glycol, polyethylene glycol, and polytetramethylene glycol.

[0052] The molecular weight of the polyether polyol (p2) can range from low to high. The molecular weight of the polyether polyol (p2) is preferably a number average molecular weight of 1,000 to 5,000. If the number average molecular weight is less than 1,000, the reactivity may be high and gelation may occur easily. If the number average molecular weight exceeds 5,000, the reactivity may be low and the cohesive force of the polyurethane polyol itself may be reduced. The amount of polyether polyol (p2) used is preferably 20 mol % to 80 mol % of the polyol constituting the urethane prepolymer P (typically, polyurethane polyol).

[0053] If necessary, the polyether polyol (p2) can be used in combination by replacing a part thereof with, for example, glycols such as ethylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerin, trimethylolpropane, and pentaerythritol, or polyamines such as ethylenediamine, N-aminoethylethanolamine, isophoronediamine, and xylylenediamine.

[0054] The polyether polyol (p2) may be a bifunctional polyether polyol alone, or a polyether polyol having a number-average molecular weight of 1000 to 5000 and at least three hydroxyl groups per molecule may be used in part or in whole. The use of a polyether polyol having an average molecular weight of 1000 to 5000 and at least three hydroxyl groups per molecule in part or in whole as the polyether polyol (p2) can achieve a good balance between adhesive strength and removability. If the number-average molecular weight of such a polyether polyol (p2) is less than 1000, the reactivity may be high and gelation may occur easily. If the number-average molecular weight of such a polyether polyol (p2) is more than 5000, the reactivity may decrease, and further, the cohesive strength of the urethane prepolymer P (typically, polyurethane polyol) itself may decrease. The number-average molecular weight of such a polyether polyol (p2) is more preferably 2500 to 3500.

[0055] As the organic polyisocyanate compound (p3), any appropriate organic polyisocyanate compound can be used as long as it does not impair the effects of the present invention. Examples of such organic polyisocyanate compound (p3) include aromatic polyisocyanates, aliphatic polyisocyanates, araliphatic polyisocyanates, and alicyclic polyisocyanates.

[0056] Examples of aromatic polyisocyanates include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0057] Examples of aliphatic polyisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0058] Examples of the aromatic aliphatic polyisocyanate include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0059] Examples of alicyclic polyisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanatemethyl)cyclohexane, and 1,4-bis(isocyanatemethyl)cyclohexane.

[0060] As the organic polyisocyanate compound (p3), a trimethylolpropane adduct, a biuret reacted with water, or a trimer having an isocyanurate ring can be used in combination.

[0061] Any suitable catalyst can be used in producing the urethane prepolymer P (typically, polyurethane polyol) as long as it does not impair the effects of the present invention. Examples of such catalysts include tertiary amine compounds and organometallic compounds.

[0062] Examples of tertiary amine compounds include triethylamine, triethylenediamine, and 1,8-diazabicyclo(5,4,0)-undecene-7(DBU).

[0063] Examples of organometallic compounds include tin-based compounds and non-tin-based compounds.

[0064] Examples of tin compounds include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin chloride, tributyltin trichloroacetate, and tin 2-ethylhexanoate.

[0065] Examples of non-tin compounds include titanium compounds such as dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride; lead compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate; iron compounds such as iron 2-ethylhexanoate and iron acetylacetonate; cobalt compounds such as cobalt benzoate and cobalt 2-ethylhexanoate; zinc compounds such as zinc naphthenate and zinc 2-ethylhexanoate; and zirconium compounds such as zirconium naphthenate.

[0066] When a catalyst is used to produce a urethane prepolymer P (typically, a polyurethane polyol), in a system containing two types of polyols, a polyester polyol (p1) and a polyether polyol (p2), problems such as gelation or cloudiness of the reaction solution are likely to occur in a system using a single catalyst due to the difference in reactivity between the two polyols. Therefore, by using two types of catalysts to obtain the urethane prepolymer P (typically, a polyurethane polyol), it becomes easier to control the reaction rate, catalyst selectivity, and the like, thereby solving these problems. Examples of such combinations of two types of catalysts include tertiary amine / organometallic, tin / non-tin, and tin / tin, with tin / tin being preferred, and a combination of dibutyltin dilaurate and tin 2-ethylhexanoate being more preferred. The weight ratio of tin 2-ethylhexanoate / dibutyltin dilaurate is preferably less than 1, more preferably 0.2 to 0.6. If the ratio is 1 or more, gelation may occur due to the balance of catalytic activity.

[0067] When a catalyst is used in producing the urethane prepolymer P (typically, a polyurethane polyol), the amount of the catalyst used is preferably 0.01% by weight to 1.0% by weight based on the total amount of the polyester polyol (a1), the polyether polyol (a2), and the organic polyisocyanate compound (a3).

[0068] When a catalyst is used in producing the urethane prepolymer P (typically, a polyurethane polyol), the reaction temperature is preferably less than 100° C., and more preferably 85° C. to 95° C. If the temperature is 100° C. or higher, it may become difficult to control the reaction rate and crosslinked structure, and it may become difficult to obtain a urethane prepolymer P (typically, a polyurethane polyol) having a predetermined molecular weight.

[0069] When producing a urethane prepolymer P (typically, a polyurethane polyol), a catalyst does not have to be used. In that case, the reaction temperature is preferably 100°C or higher, more preferably 110°C or higher. When producing a urethane prepolymer P (typically, a polyurethane polyol) in the absence of a catalyst, the reaction is preferably carried out for 3 hours or longer.

[0070] Methods for producing a urethane prepolymer P (typically, a polyurethane polyol) include, for example, 1) a method in which a polyester polyol (p1), a polyether polyol (p2), a catalyst, and an organic polyisocyanate compound (p3) are charged into a volumetric flask, and 2) a method in which a polyester polyol (p1), a polyether polyol (p2), and a catalyst are charged into a flask and the organic polyisocyanate compound (p3) is added dropwise. As a method for producing a urethane prepolymer P (typically, a polyurethane polyol), method 2) is preferred in terms of reaction control.

[0071] When producing the urethane prepolymer P (typically, polyurethane polyol), any suitable solvent can be used as long as it does not impair the effects of the present invention. Examples of such solvents include methyl ethyl ketone, ethyl acetate, toluene, xylene, and acetone. Among these solvents, toluene is preferred.

[0072] <1-1-2. Polyol A>

[0073] Examples of polyol A include polyester polyol, polyether polyol, polycaprolactone polyol, polycarbonate polyol, and castor oil polyol. Polyol A is more preferably polyester polyol or polyether polyol.

[0074] The polyester polyol can be obtained, for example, by an esterification reaction between a polyol component and an acid component.

[0075] Examples of polyol components include ethylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, glycerin, trimethylolpropane, pentaerythritol, hexanetriol, and polypropylene glycol.

[0076] Examples of the acid component include succinic acid, methylsuccinic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, dimer acid, 2-methyl-1,4-cyclohexanedicarboxylic acid, 2-ethyl-1,4-cyclohexanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and acid anhydrides thereof.

[0077] Examples of polyether polyols include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide using water, low-molecular-weight polyols (propylene glycol, ethylene glycol, glycerin, trimethylolpropane, pentaerythritol, etc.), bisphenols (bisphenol A, etc.), dihydroxybenzenes (catechol, resorcinol, hydroquinone, etc.) as initiators. Specific examples include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0078] Examples of polycaprolactone polyols include caprolactone-based polyester diols obtained by ring-opening polymerization of cyclic ester monomers such as ε-caprolactone and σ-valerolactone.

[0079] Examples of polycarbonate polyols include polycarbonate polyols obtained by polycondensation of the above polyol components with phosgene; polycarbonate polyols obtained by transesterification of the above polyol components with carbonate diesters such as dimethyl carbonate, diethyl carbonate, dipropyl carbonate, diisopropyl carbonate, dibutyl carbonate, ethylbutyl carbonate, ethylene carbonate, propylene carbonate, diphenyl carbonate, and dibenzyl carbonate; copolymer polycarbonate polyols obtained by combining two or more of the above polyol components; polycarbonate polyols obtained by esterification of the above various polycarbonate polyols with carboxyl group-containing compounds; and various of the above various Examples of the polycarbonate polyol include polycarbonate polyols obtained by etherifying polycarbonate polyols with hydroxyl group-containing compounds; polycarbonate polyols obtained by transesterifying the above-mentioned various polycarbonate polyols with ester compounds; polycarbonate polyols obtained by transesterifying the above-mentioned various polycarbonate polyols with hydroxyl group-containing compounds; polyester-based polycarbonate polyols obtained by polycondensation of the above-mentioned various polycarbonate polyols with dicarboxylic acid compounds; and copolymerized polyether-based polycarbonate polyols obtained by copolymerizing the above-mentioned various polycarbonate polyols with alkylene oxides.

[0080] Examples of castor oil-based polyols include castor oil-based polyols obtained by reacting castor oil fatty acids with the above-mentioned polyol components.Specific examples include castor oil-based polyols obtained by reacting castor oil fatty acids with polypropylene glycol.

[0081] The polyol A contains a first polyol A1 having a number average molecular weight Mn of 5000 to 20000 and a second polyol A2 having a number average molecular weight Mn of 300 to 4999. When the polyol A contains the first polyol A1 having a number average molecular weight Mn of 5000 to 20000 and the second polyol A2 having a number average molecular weight Mn of 300 to 4999, the effects of the present invention can be more effectively exhibited.

[0082] The first polyol A1 may be of only one type, or of two or more types.

[0083] The second polyol A2 may be one type only, or two or more types.

[0084] The total content of the first polyol A1 and the second polyol A2 in the polyol A is preferably 80% by weight to 100% by weight, more preferably 90% by weight to 100% by weight, even more preferably 95% by weight to 100% by weight, particularly preferably 98% by weight to 100% by weight, and most preferably substantially 100% by weight, in order to further exhibit the effects of the present invention.

[0085] The number average molecular weight Mn of the first polyol A1 is 5000 to 20000, preferably 6000 to 18000, more preferably 7000 to 16000, still more preferably 8000 to 15000, and particularly preferably 9000 to 14000. When the number average molecular weight Mn of the first polyol A1 is within the above range, the effects of the present invention can be more effectively exhibited.

[0086] The number average molecular weight Mn of the second polyol A2 is 300 to 4999, preferably 350 to 4500, more preferably 400 to 4000, still more preferably 500 to 3800, and particularly preferably 700 to 3500. When the number average molecular weight Mn of the second polyol A2 is within the above range, the effects of the present invention can be more effectively exhibited.

[0087] The weight ratio of the first polyol A1 to the second polyol A2 is preferably 1.0 ≦ (A1 / A2) ≦ 3.5, more preferably 1.0 ≦ (A1 / A2) ≦ 3.0, even more preferably 1.0 ≦ (A1 / A2) ≦ 2.5, and particularly preferably 1.0 ≦ (A1 / A2) ≦ 2.0. When the weight ratio of the first polyol A1 to the second polyol A2 is within the above range, the effects of the present invention can be more effectively exhibited.

[0088] The first polyol A1 preferably has 3 to 6 OH groups, more preferably 3 to 5 OH groups, even more preferably 3 to 4 OH groups, and particularly preferably 3 OH groups, in order to further exert the effects of the present invention.

[0089] The first polyol A1 preferably contains 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, particularly preferably 95% by weight to 100% by weight, and most preferably substantially 100% by weight of a triol having three OH groups, in order to further exert the effects of the present invention.

[0090] The second polyol A2 preferably has 3 to 6 OH groups, more preferably 3 to 5 OH groups, even more preferably 3 to 4 OH groups, and particularly preferably 3 OH groups, in order to further exert the effects of the present invention.

[0091] The second polyol A2 preferably contains 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, particularly preferably 95% by weight to 100% by weight, and most preferably substantially 100% by weight of a triol having three OH groups, in order to further exert the effects of the present invention.

[0092] <1-1-3. Polyfunctional isocyanate compound B>

[0093] The polyfunctional isocyanate compound B may be one kind or two or more kinds.

[0094] Any appropriate polyfunctional isocyanate compound that can be used in a urethanization reaction can be used as the polyfunctional isocyanate compound B. Examples of such polyfunctional isocyanate compound B include polyfunctional aliphatic isocyanate compounds, polyfunctional alicyclic isocyanates, and polyfunctional aromatic isocyanate compounds.

[0095] Examples of polyfunctional aliphatic isocyanate compounds include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0096] Examples of polyfunctional alicyclic isocyanate compounds include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.

[0097] Examples of polyfunctional aromatic diisocyanate compounds include phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.

[0098] Examples of the polyfunctional isocyanate compound B include trimethylolpropane adducts of the above-mentioned various polyfunctional isocyanate compounds, biuret compounds obtained by reacting with water, and trimers having an isocyanurate ring. These may also be used in combination.

[0099] <1-1-4. Other ingredients> The urethane-based pressure-sensitive adhesive composition may contain any appropriate other components in addition to the urethane prepolymer P, polyol A, and polyfunctional isocyanate compound B, as long as the effects of the present invention are not impaired. Examples of such other components include resin components other than the urethane prepolymer P and polyol A, crosslinking agents other than the polyfunctional isocyanate compound B, crosslinking retarders, ionic compounds, fluorine-based additives, silicone-based additives, fatty acid esters, tackifiers, inorganic fillers, organic fillers, metal powders, pigments, foil-like materials, softeners, antioxidants, conductive agents, UV absorbers, antioxidants, light stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, and catalysts.

[0100] [Ionic Compounds] When an ionic compound is contained as another component, the antistatic performance of the surface protection film according to the embodiment of the present invention can be improved.

[0101] The content of the ionic compound may be any appropriate content ratio as long as it does not impair the effects of the present invention. To further improve the antistatic performance of the surface protective film of the present invention, the content of the ionic compound relative to the total amount of urethane prepolymer P and polyol A is preferably 0.05 wt % or more, more preferably 0.10 wt % to 50 wt %, even more preferably 0.20 wt % to 30 wt %, particularly preferably 0.30 wt % to 10 wt %, and most preferably 0.50 wt % to 1 wt %. When the content of the ionic compound relative to the total amount of urethane prepolymer P and polyol A is within the above range, the antistatic performance of the surface protective film of the present invention can be further improved. If the content of the ionic compound relative to the total amount of urethane prepolymer P and polyol A is too low outside the above range, the surface protective film of the present invention may not be able to achieve sufficient antistatic performance. If the content of the ionic compound relative to the total amount of urethane prepolymer P and polyol A is too high outside the above range, the contamination of the adherend may increase.

[0102] As the ionic compound, any appropriate ionic compound can be used as long as it does not impair the effects of the present invention. The ionic compound may be one type only, or two or more types.

[0103] As the ionic compound, in terms of being able to further exhibit the effects of the present invention, preferred are ionic compounds containing at least one selected from onium cations and metal cations and a fluoroorganic anion, and ionic group-containing silicone oligomers, and in terms of being able to further improve the appearance of the pressure-sensitive adhesive layer, more preferred are ionic compounds containing at least one selected from onium cations and metal cations and a fluoroorganic anion.

[0104] The ionic compound may be an ionic liquid, which means a molten salt (ionic compound) that is liquid at 25°C.

[0105] As the ionic group-containing silicone oligomer, any suitable ionic group-containing silicone oligomer can be used as long as it does not impair the effects of the present invention. An example of an ionic group-containing silicone oligomer is "X-40-2450" manufactured by Shin-Etsu Chemical Co., Ltd.

[0106] As the onium cation, any appropriate onium cation can be used as long as it does not impair the effects of the present invention. In terms of further exhibiting the effects of the present invention, such an onium cation is preferably at least one selected from ammonium cations (nitrogen-containing onium cations), sulfonium cations (sulfur-containing onium cations), and phosphorus-containing onium cations (phosphonium cations), and more preferably ammonium cations.

[0107] As the metal cation, any appropriate metal cation can be used as long as it does not impair the effects of the present invention. In terms of being able to further exhibit the effects of the present invention, such metal cation is preferably an alkali metal cation such as a Li cation, a Na cation, or a K cation.

[0108] As the fluoroorganic anion, any appropriate fluoroorganic anion can be used as long as it does not impair the effects of the present invention. The fluoroorganic anion may be completely fluorinated (perfluorinated) or partially fluorinated.

[0109] Examples of such fluoroorganic anions include fluorinated arylsulfonates, perfluoroalkanesulfonates, bis(fluorosulfonyl)imides, bis(perfluoroalkanesulfonyl)imides, cyanoperfluoroalkanesulfonylamides, bis(cyano)perfluoroalkanesulfonylmethides, cyano-bis-(perfluoroalkanesulfonyl)methides, tris(perfluoroalkanesulfonyl)methides, trifluoroacetates, perfluoroalkylates, tris(perfluoroalkanesulfonyl)methides, and (perfluoroalkanesulfonyl)trifluoroacetamides.

[0110] Among these fluoroorganic anions, perfluoroalkylsulfonates, bis(fluorosulfonyl)imides, and bis(perfluoroalkanesulfonyl)imides are preferred, as they can further exert the effects of the present invention. More specifically, for example, trifluoromethanesulfonate, pentafluoroethanesulfonate, heptafluoropropanesulfonate, nonafluorobutanesulfonate, bis(fluorosulfonyl)imide, and bis(trifluoromethanesulfonyl)imide are preferred, and bis(fluorosulfonyl)imide and bis(trifluoromethanesulfonyl)imide are preferred.

[0111] As the ionic compound, an ionic compound composed of an onium cation and an organic fluoro anion is more preferred, as it can more effectively exhibit the effects of the present invention.

[0112] The onium cation preferably has at least one type selected from the structures represented by general formulas (1) to (4). [ka]

[0113] In general formula (1), Ra represents a hydrocarbon group having 4 to 20 carbon atoms, which may contain a heteroatom, and Rb and Rc are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a heteroatom, provided that when the nitrogen atom contains a double bond, Rc does not exist.

[0114] In general formula (2), Rd represents a hydrocarbon group having 2 to 20 carbon atoms, which may contain a heteroatom, and Re, Rf, and Rg may be the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a heteroatom.

[0115] In general formula (3), Rh represents a hydrocarbon group having 2 to 20 carbon atoms, which may contain a heteroatom, and Ri, Rj, and Rk may be the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms, which may contain a heteroatom.

[0116] In general formula (4), Z represents a nitrogen atom, a sulfur atom, or a phosphorus atom, and Rl, Rm, Rn, and Ro are the same or different and represent a hydrocarbon group having 1 to 20 carbon atoms, which may contain a heteroatom, provided that when Z is a sulfur atom, Ro does not exist.

[0117] Examples of the cation structure represented by general formula (1) include a pyridinium cation structure, a pyrrolidinium cation structure, a piperidinium cation structure, a cation structure having a pyrroline skeleton, and a cation structure having a pyrrole skeleton.

[0118] Specific examples of the cation represented by general formula (1) include pyridinium cations such as 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-hexyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, 1-octyl-4-methylpyridinium cation, 1-butyl-3,4-dimethylpyridinium cation, and 1,1-dimethylpyrrolidinium cation; 1-ethyl-1-methylpyrrolidinium cation, 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-methyl-1-pentylpyrrolidinium cation, 1-methyl-1-hexylpyrrolidinium cation, 1-methyl-1-heptylpyrrolidinium cation, 1-ethyl-1-propylpyrrolidinium cation, 1-ethyl-1-butylpyrrolidinium cation, 1-ethyl-1-pentylpyrrolidinium cation, 1-ethyl-1-hexylpyrrolidinium cation, 1-ethyl-1-heptylpyrrolidinium pyrrolidinium cations such as 1,1-dipropylpyrrolidinium cation, 1-propyl-1-butylpyrrolidinium cation, and 1,1-dibutylpyrrolidinium cation; 1-propylpiperidinium cation, 1-pentylpiperidinium cation, 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-propylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, and 1-methyl-1- piperidinium cations such as heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation, 1-ethyl-1-butylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-hexylpiperidinium cation, 1-ethyl-1-heptylpiperidinium cation, 1-propyl-1-butylpiperidinium cation, 1,1-dimethylpiperidinium cation, 1,1-dipropylpiperidinium cation, and 1,1-dibutylpiperidinium cation; 2-methyl-1-pyrroline cation;Examples include 1-ethyl-2-phenylindole cation; 1,2-dimethylindole cation; 1-ethylcarbazole cation; and cations which further contain at least one selected from the group consisting of a vinyl group (CH═CH— group) and an allyl group (CH═CH—CH— group).

[0119] Among these, in terms of further exhibiting the effects of the present invention, preferred are pyridinium cations such as 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-hexyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation; 1-ethyl-1-methylpyrrolidinium cation, 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-methyl-1-pentylpyrrolidinium cation, 1-methyl-1-hexylpyrrolidinium cation, 1-methyl-1-heptylpyrrolidinium cation, 1-ethyl-1-propylpyrrolidinium cation, 1-ethyl-1-butylpyrrolidinium cation, 1-ethyl ... and 1-ethyl-1-pentylpyrrolidinium cation. pyrrolidinium cations such as 1-ethyl-1-hexylpyrrolidinium cation and 1-ethyl-1-heptylpyrrolidinium cation; piperidinium cations such as 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-propylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, 1-methyl-1-heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation, 1-ethyl-1-butylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-hexylpiperidinium cation, 1-ethyl-1-heptylpiperidinium cation, and 1-propyl-1-butylpiperidinium cation; cations such as these cations further having at least one selected from a vinyl group (CH═CH— group) and an allyl group (CH═CH—CH— group);and the like, more preferably a 1-hexylpyridinium cation, a 1-ethyl-3-methylpyridinium cation, a 1-butyl-3-methylpyridinium cation, a 1-octyl-4-methylpyridinium cation, a 1-methyl-1-propylpyrrolidinium cation, a 1-methyl-1-propylpiperidinium cation, or a cation further having at least one selected from a vinyl group (CH═CH— group) and an allyl group (CH═CH—CH— group);

[0120] Examples of the cation structure represented by general formula (2) include an imidazolium cation structure, a tetrahydropyrimidinium cation structure, and a dihydropyrimidinium cation structure.

[0121] Specific examples of the cation represented by general formula (2) include, for example, 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-decyl-3-methylimidazolium cation, and 1-dodecyl-3-methylimidazolium. Cations, imidazolium cations such as 1-tetradecyl-3-methylimidazolium cation, 1,2-dimethyl-3-propylimidazolium cation, 1-ethyl-2,3-dimethylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, 1-hexyl-2,3-dimethylimidazolium cation; 1,3-dimethyl-1,4,5,6-tetrahydropyrimidinium cation, 1,2,3-trimethyl-1,4,5,6 tetrahydropyrimidinium cations such as 1,2,3,4-tetramethyl-1,4,5,6-tetrahydropyrimidinium cation, 1,2,3,5-tetramethyl-1,4,5,6-tetrahydropyrimidinium cation; dihydropyrimidinium cations such as 1,3-dimethyl-1,4-dihydropyrimidinium cation, 1,3-dimethyl-1,6-dihydropyrimidinium cation, 1,2,3-trimethyl-1,4-dihydropyrimidinium cation, 1,2,3-trimethyl-1,6-dihydropyrimidinium cation, 1,2,3,4-tetramethyl-1,4-dihydropyrimidinium cation, 1,2,3,4-tetramethyl-1,6-dihydropyrimidinium cation; cations such as these cations further having at least one selected from a vinyl group (CH═CH— group) and an allyl group (CH═CH—CH— group).

[0122] Among these, 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-decyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, 1-tetradecyl-3-methylimidazolium cation, and 1-methylimidazolium cation are preferred, as they can more effectively exhibit the effects of the present invention. imidazolium cations such as the methylimidazolium cation, or cations which further have at least one selected from a vinyl group (CH2=CH- group) and an allyl group (CH2=CH-CH2- group), and more preferably the 1-ethyl-3-methylimidazolium cation, the 1-hexyl-3-methylimidazolium cation, or cations which further have at least one selected from a vinyl group (CH2=CH- group) and an allyl group (CH2=CH-CH2- group).

[0123] Examples of the cation structure represented by general formula (3) include a pyrazolium cation structure and a pyrazolinium cation structure.

[0124] Specific examples of the cation represented by general formula (3) include pyrazolium cations such as a 1-methylpyrazolium cation, a 3-methylpyrazolium cation, a 1-ethyl-2-methylpyrazolinium cation, a 1-ethyl-2,3,5-trimethylpyrazolium cation, a 1-propyl-2,3,5-trimethylpyrazolium cation, and a 1-butyl-2,3,5-trimethylpyrazolium cation; pyrazolinium cations such as a 1-ethyl-2,3,5-trimethylpyrazolinium cation, a 1-propyl-2,3,5-trimethylpyrazolinium cation, and a 1-butyl-2,3,5-trimethylpyrazolinium cation; and cations in which these cations further have at least one selected from a vinyl group (CH═CH— group) and an allyl group (CH═CH—CH— group).

[0125] Examples of the cation structure represented by general formula (4) include a tetraalkylammonium cation structure, a trialkylsulfonium cation structure, a tetraalkylphosphonium cation structure, and structures in which a portion of the alkyl groups is substituted with an alkenyl group, an alkoxyl group, or an epoxy group.

[0126] Specific examples of the cation represented by general formula (4) include tetramethylammonium cation, tetraethylammonium cation, tetrabutylammonium cation, tetrapentylammonium cation, tetrahexylammonium cation, tetraheptylammonium cation, triethylmethylammonium cation, tributylethylammonium cation, trimethylpropylammonium cation, trimethyldecylammonium cation, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation, glycidyltrimethylammonium cation, diallyldimethylammonium cation, N,N-dimethyl-N-ethyl-N-propylammonium cation, N,N-dimethyl-N-ethyl-N-butylammonium cation, N,N-dimethyl-N-ethyl-N-pentylammonium cation, N,N-dimethyl-N-ethyl-N-hexylammonium cation, N,N-dimethyl-N-ethyl-N-heptylammonium cation, N,N-dimethyl-N-ethyl-N-nonylammonium cation, and N,N-dimethyl- N,N-dipropylammonium cation, N,N-diethyl-N-propyl-N-butylammonium cation, N,N-dimethyl-N-propyl-N-pentylammonium cation, N,N-dimethyl-N-propyl-N-hexylammonium cation, N,N-dimethyl-N-propyl-N-heptylammonium cation, N,N-dimethyl-N-butyl-N-hexylammonium cation, N,N-diethyl-N-butyl-N-heptylammonium cation, N,N-dimethyl-N-pentyl-N-hexylammonium cation Thione, N,N-dimethyl-N,N-dihexylammonium cation, trimethylheptylammonium cation, N,N-diethyl-N-methyl-N-propylammonium cation, N,N-diethyl-N-methyl-N-pentylammonium cation, N,N-diethyl-N-methyl-N-heptylammonium cation, N,N-diethyl-N-propyl-N-pentylammonium cation, triethylpropylammonium cation, triethylpentylammonium cation, triethylheptylammonium cation, N,Tetraalkylammonium cations such as N-dipropyl-N-methyl-N-ethylammonium cation, N,N-dipropyl-N-methyl-N-pentylammonium cation, N,N-dipropyl-N-butyl-N-hexylammonium cation, N,N-dipropyl-N,N-dihexylammonium cation, N,N-dibutyl-N-methyl-N-pentylammonium cation, N,N-dibutyl-N-methyl-N-hexylammonium cation, trioctylmethylammonium cation, N-methyl-N-ethyl-N-propyl-N-pentylammonium cation; trimethylsulfonium cation, triethylsulfonium cation, tributylsulfonium cation, trihexylsulfonium cation, trialkylsulfonium cations such as phosphonium cation, diethylmethylsulfonium cation, dibutylethylsulfonium cation, and dimethyldecylsulfonium cation; tetraalkylphosphonium cations such as tetramethylphosphonium cation, tetraethylphosphonium cation, tetrabutylphosphonium cation, tetrahexylphosphonium cation, tetraoctylphosphonium cation, triethylmethylphosphonium cation, tributylethylphosphonium cation, and trimethyldecylphosphonium cation; and cations in which these cations further have at least one selected from a vinyl group (CH=CH- group) and an allyl group (CH=CH-CH- group).

[0127] The ionic compound is preferably an ionic compound containing at least one selected from the above onium cations and metal cations and the above fluoroorganic anion, or an ionic group-containing silicone oligomer, more preferably an ionic compound containing at least one selected from the above onium cations and metal cations and the above fluoroorganic anion, and even more preferably an ionic compound containing the above onium cation and the above fluoroorganic anion.

[0128] In terms of being able to further exhibit the effects of the present invention, the ionic compound is preferably, specifically, 1-hexylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluorom ... bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyrid 1-octyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium 1-Ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-methylimidazolium heptafluoropropanesulfonate, 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-Ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-Hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-Allyl-3-methylimidazolium trifluoromethanesulfonate, 1-Allyl-3-methylimidazolium heptafluoropropanesulfonate, 1-Allyl- 3-methyl-imidazolium bis(trifluoromethanesulfonyl)imide, 1-allyl-3-methyl-imidazolium bis(fluorosulfonyl)imide, methyltrioctylammonium bis(trifluoromethanesulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, more preferably 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide,1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-allyl-3-methyl-imidazolium bis(trifluoromethanesulfonyl)imide, methyltrioctylammonium bis(trifluoromethanesulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide are preferred, and 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-allyl-3-methyl-imidazolium bis(trifluoromethanesulfonyl)imide, methyltrioctylammonium bis(trifluoromethanesulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide are particularly preferred.

[0129] The ionic compound may be commercially available or synthesized by any suitable method. For example, the ionic liquid may be synthesized by a halide method, a hydroxide method, an acid ester method, a complex formation method, a neutralization method, or the like, as described in "Ionic Liquids - The Frontline and Future of Development" (published by CMC Publishing).

[0130] [Fluorine-based additives] When a fluorine-based additive is contained as another component, it is possible to further improve the easy peelability and antistatic performance of the surface protection film according to the embodiment of the present invention.

[0131] As the fluorine-based additive, any appropriate fluorine-based additive can be used as long as it does not impair the effects of the present invention.

[0132] The fluorine-based additive may be one kind or two or more kinds.

[0133] The content of the fluorine-based additive relative to the total amount of urethane prepolymer P and polyol A is preferably 0.01% by weight or more, more preferably 0.03% by weight to 30 parts by weight, even more preferably 0.05 parts by weight to 10 parts by weight, and particularly preferably 0.05 parts by weight to 1 part by weight. When the content of the fluorine-based additive relative to the total amount of urethane prepolymer P and polyol A is within the above range, it becomes possible to further improve the easy peelability and antistatic performance of the surface protection film according to the embodiment of the present invention.

[0134] In order to further exert the effects of the present invention, the content ratio of the total amount of the fluorine-based additive and the silicone-based additive, which will be described later, to the total amount of the urethane prepolymer P and the polyol A is 0.01% by weight or more, and more preferably 0.03% by weight to 30% by weight. % and more preferably 0.05 wt. % ~10 weight % and particularly preferably 0.05 wt. % ~1 weight % is.

[0135] The fluorine-based additive may be, for example, at least one selected from a fluorine-containing compound, a hydroxyl group-containing fluorine-based compound, and a crosslinkable functional group-containing fluorine-based compound.

[0136] Examples of fluorine-containing compounds include compounds having a fluoroaliphatic hydrocarbon skeleton, fluorine-containing organic compounds obtained by copolymerizing an organic compound with a fluorine-based compound, and fluorine-containing compounds containing an organic compound. Examples of fluoroaliphatic hydrocarbon skeletons include fluoro C1-C10 alkanes such as fluoromethane, fluoroethane, fluoropropane, fluoroisopropane, fluorobutane, fluoroisobutane, fluoro t-butane, fluoropentane, and fluorohexane. Here, the term "C1-C10" means that the number of carbon atoms is 1 to 10.

[0137] A preferred embodiment of the fluorine-containing compound is an oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group ("specific fluorine-based compound"). The use of such a "specific fluorine-based compound" can improve the easy releasability and antistatic performance of the surface protection film according to the embodiment of the present invention. In particular, the combined use of such a "specific fluorine-based compound" with an ionic compound can further improve the easy releasability and antistatic performance of the surface protection film according to the embodiment of the present invention. This is presumably because the specific fluorine-based compound causes the ionic compound to be unevenly distributed on the surface side of the urethane-based pressure-sensitive adhesive layer (the side that is bonded to the adherend). Representative examples of the fluorine-containing group include fluorine-containing alkyl groups (e.g., CF3-, etc.) and / or fluorine-containing alkylene groups (e.g., -CF2-CF2-, etc.). A hydrophilic group is a group having hydrophilic properties, and hydrophilicity is translated into English as "hydrophilic," a property generally known to those skilled in the art as meaning "having an affinity for water" (see, for example, McGraw-Hill Scientific and Technical Dictionary (Revised 3rd Edition, Nikkan Kogyo Shimbun, Ltd.)). A lipophilic group is a group having lipophilic properties, and lipophilicity is translated into English as "lipophilic," a property generally known to those skilled in the art as meaning "having an affinity for oil" (see, for example, McGraw-Hill Scientific and Technical Dictionary (Revised 3rd Edition, Nikkan Kogyo Shimbun, Ltd.)).

[0138] From the viewpoint of further improving the easy releasability of the surface protection film according to the embodiment of the present invention, the fluorine-containing compound preferably has a surface tension of 19.0 mN / m to 26.0 mN / m when made into a 0.1% toluene solution (the surface tension of toluene is 27.9 mN / m). Thus, if the surface tension of the fluorine-containing compound when made into a 0.1% toluene solution is within the narrow specific range of 19.0 mN / m to 26.0 mN / m, the easy releasability of the surface protection film according to the embodiment of the present invention can be further improved.

[0139] From the viewpoint of further improving the antistatic performance of the surface protection film according to the embodiment of the present invention, the fluorine-containing compound preferably has a surface tension of 26.0 mN / m to 28.0 mN / m when dissolved in 0.1% toluene (the surface tension of toluene is 27.9 mN / m). Thus, if the surface tension of the fluorine-containing compound when dissolved in 0.1% toluene is within the narrow specific range of 26.0 mN / m to 28.0 mN / m, the antistatic performance of the surface protection film according to the embodiment of the present invention can be further improved.

[0140] As commercially available fluorine-containing compounds, for example, the following may be mentioned:

[0141] DIC Corporation's Megafuck series: Representative examples include "Megafac F-114", "Megafac F-251", "Megafac F-253", "Megafac F-281", "Megafac F-410", "Megafac F-430", "Megafac F-444", "Megafac F-477", "Megafac F-510", "Megafac F-551-A", "Megafac F-553", "Megafac F-554", "Megafac F-555-A", "Megafac F-556", "Megafac F-557", "Megafac F-558", "Megafac F-559", "Megafac F-560", and "Megafac F-561". , "Megafack F-562", "Megafack F-563", "Megafack F-565", "Megafack F-568", "Megafack F-569", "Megafack F-570", "Megafack F-576", "Megafack R-01", "Megafack R-40", "Megafack R-40-LM", "Megafack R-41", "Megafack R-41-LM", "Megafack R-94", "Megafack RS-56", "Megafack RS-72-K", "Megafack RS-75-A", "Megafack RS-75-NS", "Megafack RS-78", "Megafack RS-90", etc.

[0142] AGC Seimi Chemical Co., Ltd.'s Surflon series: Representative examples include "S-242", "S-243", and "S-386".

[0143] Sumitomo 3M FC series: Representative examples include "FC-4430" and "FC-4432".

[0144] Neos Ftergent series: Representative examples include "Ftergent 100," "Ftergent 100C," "Ftergent 110," "Ftergent 150," "Ftergent 150CH," "Ftergent 250," and "Ftergent 400SW."

[0145] Kitamura Chemical Industry Co., Ltd. PF series: Representative examples include "PF-136A", "PF-156A", "PF-151N", "PF-636", "PF-6320", "PF-656", "PF-6520", "PF-651", "PF-652", and "PF-3320".

[0146] Examples of the hydroxyl-containing fluorine-based compound include conventionally known resins, such as those described in International Publication No. 94 / 06870, Japanese Patent Application Laid-Open No. 8-12921, Japanese Patent Application Laid-Open No. 10-72569, Japanese Patent Application Laid-Open No. 4-275379, International Publication No. 97 / 11130, and International Publication No. 96 / 26254. Other hydroxyl-containing fluorine-based resins include fluoroolefin copolymers described in Japanese Patent Application Laid-Open No. 8-231919, Japanese Patent Application Laid-Open No. 10-265731, Japanese Patent Application Laid-Open No. 10-204374, and Japanese Patent Application Laid-Open No. 8-12922. Other examples include copolymers of a compound having a fluorinated alkyl group in a hydroxyl-containing compound, fluorine-containing organic compounds in which a hydroxyl-containing compound is copolymerized with a fluorine-containing compound, and fluorine-containing compounds containing a hydroxyl-containing organic compound. Commercially available examples of such hydroxyl group-containing fluorine-based compounds include those sold under the trade name "Lumiflon" (manufactured by Asahi Glass Co., Ltd.), those sold under the trade name "Cefralcoat" (manufactured by Central Glass Co., Ltd.), those sold under the trade name "Zaflon" (manufactured by Toa Gosei Co., Ltd.), and those sold under the trade name "Zeffle" (manufactured by Daikin Industries, Ltd.).

[0147] Examples of fluorine-based compounds containing crosslinkable functional groups include carboxylic acid compounds having a fluorinated alkyl group such as perfluorooctanoic acid, copolymers of compounds having a fluorinated alkyl group with a crosslinkable functional group-containing compound, fluorine-containing organic compounds obtained by copolymerizing a fluorine-containing compound with a crosslinkable functional group-containing compound, and fluorine-containing compounds containing a crosslinkable functional group-containing compound. Commercially available examples of such fluorine-based compounds containing crosslinkable functional groups include those under the trade names "Megafac F-570," "Megafac RS-55," "Megafac RS-56," "Megafac RS-72-K," "Megafac RS-75," "Megafac RS-76-E," "Megafac RS-76-NS," "Megafac RS-78," and "Megafac RS-90" (manufactured by DIC Corporation).

[0148] Among commercially available fluorine-containing compounds, a representative example of the "oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group" is the following, manufactured by DIC Corporation: "Megafac F-477" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.4 mN / m), "Megafac F-551-A" (oligomer containing fluorine and lipophilic groups, surface tension of 0.1% toluene solution = 25.6 mN / m), "Megafac F-553" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.4 mN / m), "Megafac F-554" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 25.0 mN / m), "Megafac F-555-A" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 20.4 mN / m), "Megafac F-557" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.3 mN / m), "Megafac F-559" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.1 mN / m), "Megafac F-563" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 20.2 mN / m), "Megafac F-569" (fluorine-containing and hydrophilic group-containing oligomer, surface tension of 0.1% toluene solution = 19.7 mN / m), Examples include:

[0149] [Silicone additives] When a silicone-based additive is contained as another component, it is possible to further improve the easy peelability of the surface protection film according to the embodiment of the present invention.

[0150] As the silicone-based additive, any appropriate silicone-based additive can be used as long as it does not impair the effects of the present invention.

[0151] The silicone-based additive may be of only one type, or may be of two or more types.

[0152] The content ratio of the silicone additive relative to the total amount of urethane prepolymer P and polyol A is preferably 0.01% by weight or more, more preferably 0.015% by weight to 30 parts by weight, even more preferably 0.02 parts by weight to 10 parts by weight, and particularly preferably 0.025 parts by weight to 1 part by weight. If the content ratio of the silicone additive relative to the total amount of urethane prepolymer P and polyol A is within the above range, it becomes possible to further improve the easy peelability of the surface protection film according to the embodiment of the present invention.

[0153] In order to further exert the effects of the present invention, the content ratio of the total amount of the fluorine-based additives and silicone-based additives relative to the total amount of the urethane prepolymer P and polyol A is 0.01% by weight or more, more preferably 0.03% by weight to 30 parts by weight, even more preferably 0.05 parts by weight to 10 parts by weight, and particularly preferably 0.05 parts by weight to 1 part by weight.

[0154] Any suitable silicone-based additive may be used as long as it does not impair the effects of the present invention. Examples of such silicone-based additives include reactive silicone oils and non-reactive silicone oils.

[0155] Examples of reactive silicone oils include side-chain reactive silicone oils in which an organic group is bonded as a side chain to a Si atom that participates in a siloxane bond; double-end reactive silicone oils in which an organic group is bonded to Si atoms located at both ends of the structure; single-end reactive silicone oils in which an organic group is bonded to only one of the Si atoms located at both ends of the structure; and side-chain double-end reactive silicone oils in which an organic group is bonded as a side chain to a Si atom that participates in a siloxane bond and organic groups are bonded to Si atoms located at both ends of the structure.

[0156] Examples of side-chain reactive silicone oils include amino-modified side-chain reactive silicone oils, epoxy-modified side-chain reactive silicone oils, carbinol-modified side-chain reactive silicone oils, mercapto-modified side-chain reactive silicone oils, carboxyl-modified side-chain reactive silicone oils, and methylhydrogen silicone oil-type side-chain reactive silicone oils. Examples of these commercially available products include various silicone oils available on the market as side-chain reactive silicone oils manufactured by Shin-Etsu Chemical Co., Ltd.

[0157] Examples of the dual-end reactive silicone oil include amino-modified dual-end reactive silicone oil, epoxy-modified dual-end reactive silicone oil, carbinol-modified dual-end reactive silicone oil, methacrylic-modified dual-end reactive silicone oil, polyether-modified dual-end reactive silicone oil, mercapto-modified dual-end reactive silicone oil, carboxyl-modified dual-end reactive silicone oil, phenol-modified dual-end reactive silicone oil, silanol-end dual-end reactive silicone oil, acrylic-modified dual-end reactive silicone oil, and carboxylic anhydride-modified dual-end reactive silicone oil. Commercially available products include various silicone oils available as dual-end reactive silicone oils manufactured by Shin-Etsu Chemical Co., Ltd. In particular, carbinol-modified dual-end reactive silicone oils such as "KF-6000," "KF-6001," "KF-6002," "KF-6003," and "KF-6028" manufactured by Shin-Etsu Chemical Co., Ltd. are preferably used.

[0158] Examples of single-end reactive silicone oils include single-end reactive modified type silicone oils and average single-end carboxyl modified type silicone oils. Commercially available products of these include various silicone oils available as single-end reactive silicone oils manufactured by Shin-Etsu Chemical Co., Ltd. In particular, carbinol-modified single-end reactive silicone oils such as "X-22-170BX", "X-22-170DX", and "X-22-4015" manufactured by Shin-Etsu Chemical Co., Ltd. can be preferably used.

[0159] Examples of the side chain both-end reactive silicone oil include side chain both-end reactive silicone oils with amino and methoxy modified side chains and epoxy modified side chain both-end reactive silicone oils. Examples of commercially available products of these include various silicone oils available as side chain both-end reactive silicone oils manufactured by Shin-Etsu Chemical Co., Ltd.

[0160] Examples of non-reactive silicone oils include side-chain non-reactive silicone oils in which an organic group is bonded as a side chain to a Si atom that is used for siloxane bonding, and double-end non-reactive silicone oils in which organic groups are bonded to Si atoms located at both ends of the structure.

[0161] As the side-chain type non-reactive silicone oil, for example, can be enumerated polyether-modified side-chain type non-reactive silicone oil, aralkyl-modified side-chain type non-reactive silicone oil, fluoroalkyl-modified side-chain type non-reactive silicone oil, long-chain alkyl-modified side-chain type non-reactive silicone oil, higher fatty acid ester-modified side-chain type non-reactive silicone oil, higher fatty acid-containing side-chain type non-reactive silicone oil, phenyl-modified side-chain type non-reactive silicone oil.These commercially available products can be enumerated, for example, various silicone oils that are commercially available as the side-chain type non-reactive silicone oil manufactured by Shin-Etsu Chemical Co., Ltd. In particular, polyether-modified side-chain non-reactive silicone oils such as "KF-351A," "KF-352A," "KF-353," "KF-354L," "KF-355A," "KF-615A," "KF-945," "KF-640," "KF-642," "KF-643," "KF-644," "KF-6020," "KF-6204," and "X-22-4515," manufactured by Shin-Etsu Chemical Co., Ltd., are preferably used.

[0162] Among these polyether-modified side-chain non-reactive silicone oils, those with an HLB value of preferably 8 or more, more preferably 9 or more, and even more preferably 10 or more are preferred, as they can further reduce adhesive residue. Examples of such polyether-modified side-chain non-reactive silicone oils include "KF-351A" (HLB=12), "KF-353" (HLB=10), "KF-354L" (HLB=16), "KF-355A" (HLB=12), "KF-615A" (HLB=10), "KF-640" (HLB=14), "KF-642" (HLB=12), "KF-643" (HLB=14), "KF-644" (HLB=11), and "KF-6204" (HLB=10).

[0163] Examples of the double-ended non-reactive silicone oil include polyether-modified double-ended non-reactive silicone oil. Examples of commercially available products include various silicone oils available on the market as double-ended non-reactive silicone oils manufactured by Shin-Etsu Chemical Co., Ltd. In particular, polyether-modified double-ended non-reactive silicone oils such as "KF-6004" manufactured by Shin-Etsu Chemical Co., Ltd. can be preferably used.

[0164] In addition to the above, any suitable conventional silicone additives may be used as the silicone additive. Examples of such silicone additives include siloxane bond-containing polymers other than those described above, hydroxyl group-containing silicone compounds other than those described above, and crosslinkable functional group-containing silicone compounds other than those described above.

[0165] Commercially available siloxane bond-containing polymers other than those mentioned above include, for example, the trade name "LE-302" (manufactured by Kyoeisha Chemical Co., Ltd.) and the BYK series leveling agents ("BYK-300", "BYK-301 / 302", "BYK-306", "BYK-307", "BYK-310", "BYK-315", "BYK-313", "BYK-320", "BYK-322", "BYK-323", "BYK-325", "BYK-330", "BYK-331" and "BYK-332") manufactured by BYK-Chemie Japan Co., Ltd. ", "BYK-333", "BYK-337", "BYK-341", "BYK-344", "BYK-345 / 346", "BYK-347", "BYK-348", "BYK-349", "BYK-370", "BYK-375", "BYK-377", "BYK-378", "BYK-UV3500", "BYK-UV3510", "BYK-UV3570", "BYK-3550", "BYK-SILCLEAN3700", "BYK-SILCLEAN3720", etc.), and Algin Chemie AC series leveling agents ("AC FS180", "AC FS360", "AC S20), Kyoeisha Chemical Co., Ltd.'s Polyflow series leveling agents (Polyflow KL-400X, Polyflow KL-400HF, Polyflow KL-401, Polyflow KL-402, Polyflow KL-403, Polyflow KL-404, etc.), Shin-Etsu Chemical Co., Ltd.'s KP series leveling agents (KP-323, KP-326, KP-341, KP-104 ", "KP-110", "KP-112", etc.), and leveling agents manufactured by Dow Corning Toray Co., Ltd. ("LP-7001", "LP-7002", "8032ADDITIVE", "57ADDITIVE", "L-7604", "FZ-2110", "FZ-2105", "67ADDITIVE", "8618ADDITIVE", "3ADDITIVE", "56ADDITIVE", etc.).

[0166] Examples of commercially available hydroxyl group-containing silicones other than those mentioned above include "BYK-370," "BYK-SILCLEAN3700," and "BYK-SILCLEAN3720" manufactured by BYK Japan K.K.

[0167] Other commercially available crosslinkable functional group-containing silicone compounds include, for example, "BY16-855," "SF8413," "BY16-839," "SF8421," "BY16-750," "BY16-880," and "BY16-152C" manufactured by Dow Corning Toray Co., Ltd.

[0168] [Antioxidants] The urethane-based pressure-sensitive adhesive composition may contain an antioxidant as another component from the viewpoint of suppressing deterioration of the urethane-based pressure-sensitive adhesive layer, etc. The antioxidant may be one type only, or two or more types may be used.

[0169] The antioxidant content in the urethane-based pressure-sensitive adhesive composition may be any appropriate content ratio as long as the effects of the present invention are not impaired. Such a content ratio, expressed as the antioxidant content relative to the total amount of urethane prepolymer P and polyol A, is preferably 0.01 to 10% by weight or more, more preferably 0.05 to 5% by weight, even more preferably 0.1 to 3% by weight, and particularly preferably 0.2 to 1% by weight.

[0170] Examples of antioxidants include radical chain inhibitors and peroxide decomposers.

[0171] Examples of the radical chain inhibitor include phenol-based antioxidants and amine-based antioxidants.

[0172] Examples of peroxide decomposers include sulfur-based antioxidants and phosphorus-based antioxidants.

[0173] Examples of the phenol-based antioxidant include monophenol-based antioxidants, bisphenol-based antioxidants, and polymeric phenol-based antioxidants.

[0174] Examples of monophenol-based antioxidants include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, and stearin-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate.

[0175] Examples of bisphenol antioxidants include 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), and 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane.

[0176] Examples of polymeric phenolic antioxidants include 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, 1,3,5-tris(3',5'-di-t-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, and tocophenol.

[0177] Examples of sulfur-based antioxidants include dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, and distearyl 3,3'-thiodipropionate.

[0178] Examples of phosphorus-based antioxidants include triphenyl phosphite, diphenyl isodecyl phosphite, and phenyl diisodecyl phosphite.

[0179] [Ultraviolet absorber] The urethane-based pressure-sensitive adhesive composition may contain an ultraviolet absorber as another component from the viewpoint of suppressing deterioration of the urethane-based pressure-sensitive adhesive layer, etc. The ultraviolet absorber may be one type only, or two or more types.

[0180] The content of the ultraviolet absorber in the urethane-based pressure-sensitive adhesive composition may be any appropriate content ratio as long as the effects of the present invention are not impaired. Such a content ratio, expressed as the content ratio of the ultraviolet absorber relative to the total amount of the urethane prepolymer P and the polyol A, is preferably 0.01 to 10% by weight or more, more preferably 0.05 to 5% by weight, even more preferably 0.1 to 3% by weight, and particularly preferably 0.2 to 1% by weight.

[0181] Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, salicylic acid-based ultraviolet absorbers, oxalic acid anilide-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, and triazine-based ultraviolet absorbers.

[0182] Examples of benzophenone-based ultraviolet absorbers include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, 2,2'-dihydroxy-4-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, and bis(2-methoxy-4-hydroxy-5-benzoylphenyl)methane.

[0183] Examples of the benzotriazole-based ultraviolet absorber include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)5-chlorobenzotriazole, 2-(2'-hydroxy Examples of suitable benzotriazoles include 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3'',4'',5'',6'',-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, 2,2'methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], and [2(2'-hydroxy-5'-methacryloxyphenyl)-2H-benzotriazole].

[0184] Examples of salicylic acid-based ultraviolet absorbers include phenyl salicylate, p-tert-butylphenyl salicylate, and p-octylphenyl salicylate.

[0185] Examples of cyanoacrylate ultraviolet absorbers include 2-ethylhexyl-2-cyano-3,3'-diphenylacrylate and ethyl-2-cyano-3,3'-diphenylacrylate.

[0186] [Light stabilizer] The urethane-based pressure-sensitive adhesive composition may contain a light stabilizer as another component from the viewpoint of suppressing deterioration of the urethane-based pressure-sensitive adhesive layer, etc. The light stabilizer may be one type only, or two or more types may be used.

[0187] The content of the light stabilizer in the urethane-based pressure-sensitive adhesive composition may be any appropriate content ratio as long as the effects of the present invention are not impaired. Such a content ratio, expressed as the content ratio of the light stabilizer relative to the total amount of the urethane prepolymer P and the polyol A, is preferably 0.01 to 10% by weight or more, more preferably 0.05 to 5% by weight, even more preferably 0.1 to 3% by weight, and particularly preferably 0.2 to 1% by weight.

[0188] Examples of the light stabilizer include hindered amine light stabilizers and ultraviolet stabilizers.

[0189] Examples of the hindered amine light stabilizer include bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate.

[0190] Examples of ultraviolet stabilizers include nickel bis(octylphenyl) sulfide, [2,2'-thiobis(4-tert-octylphenolate)]-n-butylamine nickel, nickel complex-3,5-di-tert-butyl-4-hydroxybenzyl-phosphate monoethylate, nickel-dibutyldithiocarbamate, benzoate-type quenchers, and nickel-dibutyldithiocarbamate.

[0191] [Fatty acid ester] The urethane-based pressure-sensitive adhesive composition may contain a fatty acid ester as another component from the viewpoint of improving the wettability of the urethane-based pressure-sensitive adhesive layer, etc. The fatty acid ester may be one type only, or two or more types.

[0192] The number-average molecular weight Mn of the fatty acid ester is preferably 200 to 400, more preferably 210 to 395, even more preferably 230 to 380, particularly preferably 240 to 360, and most preferably 250 to 350. By adjusting the number-average molecular weight Mn of the fatty acid ester within the above range, the wetting speed can be further improved. If the number-average molecular weight Mn of the fatty acid ester is too small, the wetting speed may not be improved even if a large amount is added. If the number-average molecular weight Mn of the fatty acid ester is too large, the curing properties of the adhesive during drying may be deteriorated, which may have an adverse effect not only on the wetting properties but also on other adhesive properties.

[0193] As the fatty acid ester, any appropriate fatty acid ester can be used as long as it does not impair the effects of the present invention. Examples of such fatty acid esters include polyoxyethylene bisphenol A laurate, butyl stearate, 2-ethylhexyl palmitate, 2-ethylhexyl stearate, behenic acid monoglyceride, cetyl 2-ethylhexanoate, isopropyl myristate, isopropyl palmitate, cholesteryl isostearate, lauryl methacrylate, coconut fatty acid methyl ester, methyl laurate, methyl oleate, methyl stearate, myristyl myristate, octyldodecyl myristate, pentaerythritol monooleate, pentaerythritol monostearate, pentaerythritol tetrapalmitate, stearyl stearate, isotridecyl stearate, 2-ethylhexanoic acid triglyceride, butyl laurate, and octyl oleate.

[0194] ≪1-2. Base material layer≫ The thickness of the substrate layer may be any appropriate thickness depending on the application. The thickness of the substrate layer is preferably 5 μm to 300 μm, more preferably 10 μm to 250 μm, still more preferably 15 μm to 200 μm, and particularly preferably 20 μm to 150 μm.

[0195] The substrate layer may be a single layer or a laminate of two or more layers. The substrate layer may be stretched.

[0196] Any appropriate material can be used as the material for the substrate layer depending on the application. Examples include plastic, paper, metal film, nonwoven fabric, etc. Plastic is preferred. The substrate layer may be made of one material or two or more materials. For example, it may be made of two or more plastics.

[0197] Examples of the plastics include polyester resins, polyamide resins, and polyolefin resins. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyolefin resins include homopolymers of olefin monomers and copolymers of olefin monomers. Specific examples of polyolefin resins include homopolypropylene; propylene copolymers such as block copolymers, random copolymers, and graft copolymers containing ethylene as a copolymerization component; reactor TPO; ethylene polymers such as low-density, high-density, linear low-density, and ultra-low-density copolymers; and ethylene copolymers such as ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-butyl acrylate copolymers, ethylene-methacrylic acid copolymers, and ethylene-methyl methacrylate copolymers.

[0198] The substrate layer may contain any appropriate additives as needed. Examples of additives that may be contained in the substrate layer include antioxidants, UV absorbers, light stabilizers, antistatic agents, fillers, and pigments. The type, number, and amount of additives that may be contained in the substrate layer may be appropriately set depending on the purpose. In particular, when the material of the substrate layer is plastic, it is preferable to contain some of the above-mentioned additives for the purpose of preventing deterioration, etc. From the viewpoint of improving weather resistance, etc., particularly preferred additives include antioxidants, UV absorbers, light stabilizers, and fillers.

[0199] Any suitable antioxidant can be used. Examples of such antioxidants include phenolic antioxidants, phosphorus-based processing heat stabilizers, lactone-based processing heat stabilizers, sulfur-based heat stabilizers, and phenol-phosphorus-based antioxidants. The content of the antioxidant is preferably 1% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.01% by weight to 0.2% by weight of the base resin of the substrate layer (when the substrate layer is a blend, the blend is the base resin).

[0200] Any suitable ultraviolet absorber may be used as the ultraviolet absorber. Examples of such ultraviolet absorbers include benzotriazole-based ultraviolet absorbers, triazine-based ultraviolet absorbers, and benzophenone-based ultraviolet absorbers. The content of the ultraviolet absorber is preferably 2% by weight or less, more preferably 1% by weight or less, and even more preferably 0.01% by weight to 0.5% by weight of the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).

[0201] Any appropriate light stabilizer can be used as the light stabilizer. Examples of such light stabilizers include hindered amine light stabilizers and benzoate light stabilizers. The content of the light stabilizer is preferably 2% by weight or less, more preferably 1% by weight or less, and even more preferably 0.01% by weight to 0.5% by weight of the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).

[0202] Any appropriate filler can be used as the filler. Examples of such fillers include inorganic fillers. Specific examples of inorganic fillers include carbon black, titanium oxide, and zinc oxide. The content of the filler is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 0.01% by weight to 10% by weight, of the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).

[0203] Further, as additives, inorganic, low-molecular-weight, and high-molecular-weight antistatic agents such as surfactants, inorganic salts, polyhydric alcohols, metal compounds, and carbon are preferred for the purpose of imparting antistatic properties. In particular, high-molecular-weight antistatic agents and carbon are preferred from the viewpoints of preventing contamination and maintaining adhesiveness.

[0204] 2. Surface protection film manufacturing method The surface protective film of the present invention can be produced by any appropriate method. Examples of such a production method include (1) A method of applying a solution or a hot melt of a material for forming the adhesive layer onto a substrate layer; (2) A method in which a pressure-sensitive adhesive layer formed by coating a separator is transferred onto a substrate layer in accordance with the method. (3) A method of forming and applying a material for forming a pressure-sensitive adhesive layer onto a substrate layer by extrusion; (4) A method of extruding a substrate layer and a pressure-sensitive adhesive layer in two or more layers. (5) A method of laminating a single layer of an adhesive layer onto a substrate layer, or a method of laminating a double layer of an adhesive layer together with a laminate layer, (6) A method of laminating a pressure-sensitive adhesive layer and a base layer-forming material such as a film or laminate layer in two or more layers. The above-mentioned manufacturing method can be carried out according to any suitable manufacturing method.

[0205] Examples of the coating method that can be used include roll coater method, comma coater method, die coater method, reverse coater method, silk screen method, and gravure coater method.

[0206] ≪≪3. Uses of surface protection film≫≫ The surface protection film according to the embodiment of the present invention can be used for any suitable application. Preferably, the surface protection film of the present invention causes very little contamination to the adherend and preferably has excellent wettability and reworkability, and is therefore preferably used for surface protection of, for example, optical components and electronic components. Examples of optical components include LCDs, touch panels using LCDs, color filters used in LCDs, polarizing plates, and the like.

[0207] Components to which the surface protection film according to the embodiment of the present invention is attached, such as optical components and electronic components, can have the attached surface protection film repeatedly attached and peeled off by hand.

[0208] That is, an optical member according to an embodiment of the present invention has the surface protection film of the present invention attached thereto, and an electronic member according to an embodiment of the present invention has the surface protection film of the present invention attached thereto. [Example]

[0209] The present invention will be specifically described below using examples, but the present invention is not limited to these examples. The test and evaluation methods used in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.

[0210] <Adhesion to glass> The surface protection film (25 mm wide x 140 mm long) from which the separator had been removed was attached to glass (soda-lime glass, manufactured by Matsunami Glass Industry Co., Ltd.) using a 2 kg hand roller with one stroke. The film was then left at an ambient temperature of 23°C for 30 minutes. The resulting evaluation sample was measured using a tensile tester. The tensile tester used was an Autograph AG-Xplus HS 6000 mm / min high-speed model (AG-50NX plus) manufactured by Shimadzu Corporation. After the evaluation sample was placed in the tensile tester, the tensile test was initiated. The test conditions were a peel angle of 180° and a peel speed (pulling rate) of 300 mm / min. The load applied when peeling the surface protection film from the glass was measured, and the average load was used as the adhesive strength (peel force) of the surface protection film to glass.

[0211] <Residual adhesion rate to glass> A surface protection film was applied to the entire surface of a glass plate (1.35 mm x 10 cm x 10 cm, manufactured by Matsunami Glass Co., Ltd.) using a hand roller. After storing the plate for 24 hours at 23°C and 55% RH, the surface protection film was peeled off at a peel angle of 180° and a speed of 0.3 m / min. A 19 mm-wide No. 31B tape (manufactured by Nitto Denko Corporation, substrate thickness: 25 μm) cut to a length of 150 mm was applied to the plate using a 2.0 kg roller at 23°C and 55% RH. After aging for 30 minutes at 23°C and 55% RH, the plate was subjected to a tensile test using a Shimadzu Autograph AG-Xplus HS 6000 mm / min high-speed model (AG-50NX plus) at a peel angle of 180° and a pulling speed of 300 mm / min to measure the adhesive strength. Separately, the adhesive strength of a 19 mm wide No. 31B tape was measured on a glass plate that had not been treated as described above, and the residual adhesive rate was calculated using the following formula. Residual adhesion rate (%) = (Adhesive strength of No. 31B to glass plate after surface protection film peeling / Adhesive strength of No. 31B to glass plate) x 100 This residual adhesion rate is an index of the degree to which the adhesive component of the surface protection film is transferred to the surface of the adherend and contaminates it. The higher the residual adhesion rate, the better the surface protection film is that it does not contaminate the adherend, and the lower the residual adhesion rate, the more the surface of the adherend is contaminated with adhesive components and the like.

[0212] <Glass peeling electrostatic voltage resistance> The surface protection film with the separator removed was cut to a size of 70 mm wide and 100 mm long and pressed onto the surface of glass (soda-lime glass, manufactured by Matsunami Glass Industry Co., Ltd.) with a hand roller, so that one end of the surface protection film protruded 30 mm beyond the edge of the adherend. This sample was left for one day in an environment of 23°C and 50% RH and then set in a predetermined position on a sample fixing table with a height of 20 mm. The end of the surface protection film protruding 30 mm from the adherend was fixed to an automatic winder (not shown), and the film was peeled at a peel angle of 150° and a peel rate of 30 m / min. The potential generated on the adherend surface during this process was measured as the "peeling electrification voltage" using a potential meter (manufactured by Shishido Electrostatics Co., Ltd., model "STATIRON DZ-4") fixed 30 mm above the center of the adherend. Measurements were performed in an environment of 23°C and 50% RH.

[0213] <Haze> The urethane-based pressure-sensitive adhesive composition was coated on the release-treated surface of a 75 μm-thick polyester film (trade name: Diafoil MRF75, manufactured by Mitsubishi Chemical Corporation) with one side treated for release with silicone, and dried under the conditions of Examples and Comparative Examples to prepare a urethane-based pressure-sensitive adhesive layer. Next, the surface of the urethane-based pressure-sensitive adhesive layer was covered with a 75 μm-thick polyester film (trade name: Diafoil MRE75, manufactured by Mitsubishi Chemical Corporation) with one side treated for release with silicone, with the release-treated surface of the polyester film facing the urethane-based pressure-sensitive adhesive layer, and the resulting mixture was aged at room temperature for 5 days. Two pieces of 50 mm x 50 mm cardboard with a 20 mm x 20 mm hole punched in the center were prepared, and the sample was attached to one of them using a hand roller with one stroke, and then the other was attached. The haze of the evaluation sample obtained as described above was measured using "HM-150N" manufactured by Murakami Color Research Laboratory.

[0214] <Can the adhesive be applied thickly?> In each of the examples and comparative examples, the urethane-based adhesive solution was applied to a substrate made of polyester resin (product name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation), dried, and it was observed whether an adhesive layer with a thickness of 75 μm was obtained after drying. ◯: A pressure-sensitive adhesive layer having a thickness of 75 μm after drying was formed. ×: A pressure-sensitive adhesive layer having a thickness of 75 μm after drying could not be formed.

[0215] [Production Example 1]: Production of urethane prepolymer A polymerization experiment apparatus equipped with a 1 L round-bottom separable flask, a separable cover, a separatory funnel, a thermometer, a nitrogen inlet tube, a Liebig condenser, a vacuum seal, a stirring rod, and a stirring blade was charged with 150 g of polypropylene glycol (product name "Sannyx PP-2000", manufactured by Sanyo Chemical Industries, Ltd.), 150 g of polyester polyol (product name "Kuraray Polyol P-2010", manufactured by Kuraray Co., Ltd.), 110 g of toluene (manufactured by Tosoh Corporation) as a solvent, and 0.041 g of dibutyltin(IV) dilaurate (manufactured by Wako Pure Chemical Industries, Ltd.) as a catalyst, and the mixture was purged with nitrogen at room temperature for 1 hour while stirring. Then, under nitrogen flow and stirring, 33.5 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosoh Corporation) was added. The solution temperature in the experimental apparatus was maintained at 90±2°C using a water bath and held for 4 hours. Then, 74.9 g of polypropylene glycol (product name "GP1000", manufactured by Sanyo Chemical Industries, Ltd.) was added. The solution temperature in the experimental apparatus was maintained at 90±2°C using a water bath and held for 2 hours. Then, 25.4 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosoh Corporation) was added. The solution temperature in the experimental apparatus was maintained at 90±2°C using a water bath and held for 2 hours, yielding a urethane prepolymer solution. During the polymerization, toluene was added dropwise as needed to control the temperature and prevent a decrease in stirrability due to increased viscosity. The total amount of toluene added was 320 g. The solids concentration of the urethane prepolymer solution was 50 wt%. This urethane prepolymer was used in the examples and comparative examples.

[0216] Example 1 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP4000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 4,000) as a polyol having three hydroxyl groups, 8.6 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying would be 75 μm, and the coating was cured and dried under conditions of a drying temperature of 130°C and a drying time of 3 minutes to produce an adhesive layer made of the adhesive composition (1). Next, the silicone-treated side of a release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of a polyester resin with one side silicone-treated and having a thickness of 25 μm was laminated to the surface of the obtained adhesive layer to obtain a surface protection film (1). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0217] Example 2 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 10.1 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (2). The silicone-treated surface of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (2). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0218] Example 3 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10000), a polyol having three hydroxyl groups, as a polyol, 15 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Mn = 3000), a polyol having three hydroxyl groups, 5 parts by weight of Sannix GP1000 (manufactured by Sanyo Chemical Industries, Mn = 1000), 12.9 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narsem ferric iron (manufactured by Nippon Chemical Industries Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (3). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (3). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0219] Example 4 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 18 parts by weight of Sannix GP3000 (Sanyo Chemical Industries, Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 2 parts by weight of Sannix GP600 (Sanyo Chemical Industries, Ltd., Mn = 600) as a polyol having three hydroxyl groups, 12.7 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (4). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain a surface protection film (4). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0220] Example 5 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 18 parts by weight of Sannix GP3000 (Sanyo Chemical Industries, Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 2 parts by weight of Sannix GP400 (Sanyo Chemical Industries, Ltd., Mn = 400) as a polyol having three hydroxyl groups, 13.8 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narsem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (5). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (5). Aging was performed at room temperature for 5 days, and evaluation was then performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0221] Example 6 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 35 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 15 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 9.1 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying would be 75 μm, and the coating was cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (6). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (6). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0222] Example 7 A urethane adhesive solution was obtained by diluting 60 parts by weight of urethane prepolymer, 25 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 15 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 8.5 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (7). The silicone-treated surface of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (7). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0223] Example 8 A urethane adhesive solution was obtained by diluting 60 parts by weight of urethane prepolymer, 28 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 12 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 7.8 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem Ferric (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying would be 75 μm, and the coating was cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (8). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (8). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0224] Example 9 A urethane adhesive solution was obtained by diluting 80 parts by weight of urethane prepolymer, 12 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 8 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 5.8 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (9). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (9). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0225] Example 10 A urethane adhesive solution was obtained by diluting 80 parts by weight of urethane prepolymer, 15 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 5 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 5.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of the adhesive composition (10). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain a surface protection film (10). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0226] Example 11 A urethane adhesive solution was obtained by diluting 95 parts by weight of urethane prepolymer, 3 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 2 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 3.6 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (11). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain a surface protection film (11). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0227] Example 12 A urethane adhesive solution was obtained by diluting 95 parts by weight of urethane prepolymer, 3.5 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 1.5 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 3.5 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (12). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain a surface protection film (12). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0228] Example 13 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3015 (manufactured by Asahi Glass Co., Ltd., Mn = 15000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3000) as a polyol having three hydroxyl groups, 9.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (13). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (13). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0229] Example 14 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3008 (manufactured by Asahi Glass Co., Ltd., Mn=8000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.8 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem Ferric (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (14). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce surface protection film (14). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0230] Example 15 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3006 (manufactured by Asahi Glass Co., Ltd., Mn = 5000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3000) as a polyol having three hydroxyl groups, 12.7 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (15). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce surface protection film (15). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 1.

[0231] Example 16 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn = 3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.05 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst were diluted with ethyl acetate to a total solids content of 50% by weight to obtain a urethane adhesive solution. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (16). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce surface protection film (16). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0232] Example 17 A urethane adhesive solution was prepared by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.1 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (17). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce surface protection film (17). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0233] Example 18 A urethane adhesive solution was prepared by diluting 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (18). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce surface protection film (18). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0234] Example 19 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn = 3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1.0 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst were diluted with ethyl acetate to a total solids content of 50% by weight to obtain a urethane adhesive solution. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (19). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce surface protection film (19). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0235] Example 20 The mixture contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 15 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 5 parts by weight of Sannix GP1000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=1000) as a polyol having three hydroxyl groups, and an isocyanate compound (Colonel) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 12.9 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (20). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (20). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0236] Example 21 The mixture contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 18 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 2 parts by weight of Sannix GP600 (manufactured by Sanyo Chemical Industries, Ltd., Mn=600) as a polyol having three hydroxyl groups, and an isocyanate compound (Coronate) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 12.7 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (21). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (21). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0237] Example 22 The mixture contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 18 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 2 parts by weight of Sannix GP400 (manufactured by Sanyo Chemical Industries, Ltd., Mn=400) as a polyol having three hydroxyl groups, and an isocyanate compound (Coronate) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 13.8 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.) as an antioxidant, 0.5 parts by weight of Irganox 1010 (BASF) as an ionic compound, and 0.03 parts by weight of Nursem ferric (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", 75 μm thick, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (22). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (22). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0238] Example 23 A urethane adhesive solution was prepared by diluting 80 parts by weight of urethane prepolymer, 15 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 5 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 5.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (23). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to obtain surface protection film (23). Aging was performed at room temperature for 5 days, and then evaluation was performed. The release sheet was peeled off immediately before evaluation. The results are shown in Table 2.

[0239] Example 24 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl-3-methyl-2-propanol as an ionic compound. A urethane adhesive solution was prepared by diluting 0.05 parts by weight of methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of the fluorine-based oligomer Megafac F-477 (manufactured by DIC Corporation), 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (24). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (24). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0240] Example 25 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.1 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of the fluorine-based oligomer Megafac F-477 (DIC Corporation), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (25). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (25). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0241] Example 26 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of the fluorine-based oligomer Megafac F-477 (DIC Corporation), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (26). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (26). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0242] Example 27 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 1.0 part by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 part by weight of the fluorine-based oligomer Megafac F-477 (DIC Corporation), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (27). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (27). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0243] Example 28 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl-3-methyl-2-propanol as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.05 parts by weight of the fluorine-based oligomer Megafac F-477 (manufactured by DIC Corporation), 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (28). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (28). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0244] Example 29 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.5 parts by weight of the fluorine-based oligomer Megafac F-477 (DIC Corporation), 0.5 parts by weight of the antioxidant Irganox 1010 (BASF Corporation), and 0.03 parts by weight of the catalyst Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (29). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (29). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0245] Example 30 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 1.0 parts by weight of the fluorine-based oligomer Megafac F-477 (DIC Corporation), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (30). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (30). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0246] Example 31 The mixture consisted of 50 parts by weight of urethane prepolymer, 35 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 15 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 9.1 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl-3-methyl-2-propanol as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of the fluorine-based oligomer Megafac F-477 (manufactured by DIC Corporation), 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (31). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (31). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0247] Example 32 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl-3-methyl-2-propanol as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.05 parts by weight of the fluorine-based oligomer Megafac F-563 (manufactured by DIC Corporation), 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (32). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (32). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0248] Example 33 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of the fluorine-based oligomer Megafac F-563 (DIC Corporation), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (33). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (33). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0249] Example 34 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.5 parts by weight of the fluorine-based oligomer Megafac F-563 (DIC Corporation), 0.5 parts by weight of the antioxidant Irganox 1010 (BASF Corporation), and 0.03 parts by weight of the catalyst Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (34). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (34). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0250] Example 35 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 1.0 parts by weight of the fluorine-based oligomer Megafac F-563 (DIC Corporation), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (35). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (35). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0251] Example 36 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.5 parts by weight of the fluorine-based oligomer Megafac F-569 (DIC Corporation), 0.5 parts by weight of the antioxidant Irganox 1010 (BASF Corporation), and 0.03 parts by weight of the catalyst Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (36). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (36). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0252] Example 37 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.5 parts by weight of the fluorine-based oligomer Megafac F-552 (DIC Corporation), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (37). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (37). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0253] Example 38 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.5 parts by weight of the fluorine-based oligomer Megafac F-559 (DIC Corporation), 0.5 parts by weight of the antioxidant Irganox 1010 (BASF Corporation), and 0.03 parts by weight of the catalyst Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (38). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (38). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0254] Example 39 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of 3-methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.5 parts by weight of the fluorine-based oligomer Megafac F-556 (DIC Corporation), 0.5 parts by weight of the antioxidant Irganox 1010 (BASF Corporation), and 0.03 parts by weight of the catalyst Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (39). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (39). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 3.

[0255] Example 40 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of luimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-containing reactive silicone oil X-22-4015 (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 ° C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (40). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (40). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0256] Example 41 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of methylpropional as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of thlylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-containing reactive silicone oil KF6001 (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 ° C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (41). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (41). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0257] Example 42 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3- A urethane adhesive solution was prepared by diluting 0.5 parts by weight of methylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-containing reactive silicone oil KF6002 (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric salt (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 ° C for 3 minutes to prepare an adhesive layer composed of adhesive composition (42). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (42). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0258] Example 43 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of methylpropional as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of thlylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-containing reactive silicone oil KF6028 (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 ° C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (43). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (43). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0259] Example 44 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of methylpropional as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of thiolimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-free non-reactive silicone oil KF643 (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric salt (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 °C for 3 minutes to prepare an adhesive layer composed of adhesive composition (44). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (44). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0260] Example 45 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of methylpropional as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of thiolimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-free non-reactive silicone oil KF640 (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric salt (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 ° C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (45). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (45). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0261] Example 46 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of luimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-free non-reactive silicone oil KF615A (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of adhesive composition (46). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (46). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0262] Example 47 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of luimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-free non-reactive silicone oil KF352A (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 °C for 3 minutes to prepare an adhesive layer composed of adhesive composition (47). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (47). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0263] Example 48 The mixture consisted of 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of methylpropional as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of thlylimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of hydroxyl-free non-reactive silicone oil KF945 (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric salt (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 °C for 3 minutes to prepare an adhesive layer composed of adhesive composition (48). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (48). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0264] Example 49 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of luimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.05 parts by weight of hydroxyl-free non-reactive silicone oil KF615A (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Nursem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 °C for 3 minutes to prepare an adhesive layer composed of adhesive composition (49). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (49). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0265] Example 50 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl-3-methylpropional as an ionic compound. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of imidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.025 parts by weight of hydroxyl-free non-reactive silicone oil KF615A (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric salt (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130 ° C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (50). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (50). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0266] Example 51 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 1-ethyl-3-methylpropional as an ionic compound, and 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent. A urethane adhesive solution was prepared by diluting 0.5 parts by weight of luimidazolium bis(trifluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.), 0.01 parts by weight of hydroxyl-free non-reactive silicone oil KF615A (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric oxide (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of adhesive composition (51). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (51). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0267] Example 52 The composition contained 50 parts by weight of urethane prepolymer, 30 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) as a polyol having three hydroxyl groups, 20 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) as a polyol having three hydroxyl groups, 10.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and 1-ethyl-3-methylimidazolium bis(trifluoromethyl) ... A urethane-based adhesive solution was prepared by diluting 0.5 parts by weight of ethanesulfonylimide (AS110, Dai-ichi Kogyo Seiyaku Co., Ltd.), 0.1 parts by weight of the fluorine-based oligomer Megafac F-563 (DIC Corporation), 0.025 parts by weight of the hydroxyl-free non-reactive silicone oil KF615A (Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric salt (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (52). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (52). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 4.

[0268] Comparative Example 1 A urethane-based adhesive solution was prepared by diluting 100 parts by weight of a urethane prepolymer, 2.9 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries Co., Ltd.) as a crosslinker, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem Ferric (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," 75 μm thick, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at 130°C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (C1). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (C1). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0269] Comparative Example 2 50 parts by weight of urethane prepolymer, 35 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10000) as a polyol having three hydroxyl groups, 13 parts by weight of Sannix GP3000 (Sanyo Chemical Industries, Ltd., Mn = 3000) as a polyol having three hydroxyl groups, 13 parts by weight of Sannix GP250 (Sanyo Chemical Industries, Ltd., Mn = 250) as a polyol having three hydroxyl groups, 15.6 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narsem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst. The mixture was diluted with ethyl acetate to a total solids content of 50% by weight to obtain a urethane adhesive solution. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of the adhesive composition (C2). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce a surface protection film (C2). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0270] Comparative Example 3 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 40 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 10 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 8.1 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Nursem Ferric (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of the adhesive composition (C3). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce a surface protection film (C3). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0271] Comparative Example 4 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 40 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000), a polyol having three hydroxyl groups, as a polyol, 5 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Mn = 3,000), a polyol having three hydroxyl groups, 5 parts by weight of Sannix GP1000 (manufactured by Sanyo Chemical Industries, Mn = 1,000), 10.8 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narsem ferric iron (manufactured by Nippon Chemical Industries Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of the adhesive composition (C4). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce a surface protection film (C4). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0272] Comparative Example 5 A urethane adhesive solution was obtained by diluting 50 parts by weight of urethane prepolymer, 24 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 26 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 11.3 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of the adhesive composition (C5). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce a surface protection film (C5). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0273] Comparative Example 6 A urethane-based adhesive solution was prepared by diluting 50 parts by weight of urethane prepolymer, 50 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000), a polyol having three hydroxyl groups, 6.0 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinker, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem Ferric (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", 75 μm thick, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at 130 °C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (C6). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (C6). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0274] Comparative Example 7 A urethane-based adhesive solution was prepared by diluting 30 parts by weight of urethane prepolymer, 70 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000), a polyol having three hydroxyl groups, 7.2 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinker, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem Ferric (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", 75 μm thick, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at 130 °C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (C7). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (C7). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0275] Comparative Example 8 A urethane-based adhesive solution was prepared by diluting 10 parts by weight of urethane prepolymer, 90 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000), a polyol having three hydroxyl groups, 8.5 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinker, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem Ferric (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S", 75 μm thick, Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at 130 °C for 3 minutes to prepare an adhesive layer composed of the adhesive composition (C8). Next, the silicone-treated side of a 25 μm thick release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (C8). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0276] Comparative Example 9 A urethane adhesive solution was obtained by diluting 30 parts by weight of urethane prepolymer, 40 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 30 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 13.4 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of adhesive composition (C9). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce a surface protection film (C9). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0277] Comparative Example 10 A urethane adhesive solution was obtained by diluting 10 parts by weight of urethane prepolymer, 50 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn = 10,000) as a polyol having three hydroxyl groups, 40 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Co., Ltd., Mn = 3,000) as a polyol having three hydroxyl groups, 16.7 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, and 0.03 parts by weight of Narcem ferric iron (manufactured by Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. The urethane-based adhesive solution was then applied to a polyester resin substrate (trade name "T100-75S," thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a dry thickness of 75 μm, and cured and dried at a drying temperature of 130°C for 3 minutes to produce an adhesive layer made of the adhesive composition (C10). The silicone-treated surface of a 25 μm-thick release sheet (trade name "MRF25," thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then bonded to the surface of the resulting adhesive layer to produce a surface protection film (C10). The film was aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before evaluation. The results are shown in Table 5.

[0278] Comparative Example 11 A urethane adhesive solution was obtained by diluting 50 parts by weight of Preminol S3011 (Asahi Glass Co., Ltd., Mn=10000), a polyol having three hydroxyl groups, 50 parts by weight of Sannix GP3000 (Sanyo Chemical Co., Ltd., Mn=3000), a polyol having three hydroxyl groups, 19.3 parts by weight of an isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.5 parts by weight of Irganox 1010 (BASF) as an antioxidant, and 0.03 parts by weight of Narcem Ferric (Nippon Chemical Industry Co., Ltd.) as a catalyst with ethyl acetate to a total solids content of 50% by weight. We then attempted to apply the urethane adhesive solution to a polyester resin substrate (product name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) and dry it to produce a 75 μm thick adhesive layer, but the viscosity of the urethane adhesive solution was low and we were unable to achieve such a thick film. The results are shown in Table 5.

[0279] [Table 1]

[0280] [Table 2]

[0281] [Table 3]

[0282] [Table 4]

[0283] [Table 5]

[0284] Examples 53 to 104 The separator was peeled off from each of the surface protection films with separators obtained in Examples 1 to 52, and the film was attached to a polarizing plate (manufactured by Nitto Denko Corporation, product name "TEG1465DUHC"), which is an optical component, to obtain an optical component with a surface protection film attached.

[0285] Examples 105 to 156 For each of the surface protection films with separators obtained in Examples 1 to 52, the separator was peeled off and the film was attached to a conductive film (manufactured by Nitto Denko Corporation, product name "ELECRYSTA V270L-TFMP"), which is an electronic component, to obtain an electronic component with a surface protection film attached. [Industrial Applicability]

[0286] The surface protective film of the present invention can be used for any suitable application, and is preferably used for protecting the surfaces of optical members and electronic members. [Explanation of symbols]

[0287] 1 Base material layer 2. Adhesive layer 10 Surface protection film

Claims

1. A surface protection film including a urethane-based pressure-sensitive adhesive layer, the urethane-based pressure-sensitive adhesive layer is composed of a urethane-based pressure-sensitive adhesive formed from a urethane-based pressure-sensitive adhesive composition, The urethane-based pressure-sensitive adhesive composition contains a urethane prepolymer P, a polyol A, and a polyfunctional isocyanate compound B, the urethane-based pressure-sensitive adhesive composition contains an ionic compound, and the content of the ionic compound relative to the total amount of the urethane prepolymer P and the polyol A is 0.05% by weight to 10% by weight; The urethane prepolymer P is a urethane prepolymer obtained by reacting a polyester polyol (p1) having a number average molecular weight of 500 to 5000, a polyether polyol (p2) having a number average molecular weight of 1000 to 5000, and an organic polyisocyanate compound (p3), the weight ratio of the urethane prepolymer P to the polyol A is P:A=(50 to 90):(10 to 50); The polyol A includes one or more first polyols A1 and one or more second polyols A2, The first polyol A1 is a polyether polyol having 3 to 6 OH groups and a number average molecular weight Mn of 5,000 to 20,000; The second polyol A2 is a polyether polyol having 3 to 6 OH groups and a number average molecular weight Mn of 300 to 4000; the total content of the first polyol A1 and the second polyol A2 in the polyol A is 98% by weight to 100% by weight, a weight ratio of the first polyol A1 to the second polyol A2 is 1.0≦(A1 / A2)≦2.0; the content ratio of the polyfunctional isocyanate compound B in the urethane-based pressure-sensitive adhesive composition is 2.5 parts by weight to 40 parts by weight based on 100 parts by weight of the urethane prepolymer P; Surface protection film.

2. The surface protection film according to claim 1, wherein the urethane-based pressure-sensitive adhesive composition comprises at least one selected from the group consisting of a fluorine-based additive and a silicone-based additive, and the content ratio of the total amount of the fluorine-based additive and the silicone-based additive to the total amount of the urethane prepolymer P and the polyol A is 0.01% by weight to 10% by weight.

3. 3. The surface protection film according to claim 1, wherein the urethane-based pressure-sensitive adhesive layer is attached to a glass plate and, after 30 minutes at 23° C., the peel strength when peeled from the glass plate at a peel angle of 180° and a peel speed of 300 mm / min is 0.5 gf / 25 mm to 2.0 gf / 25 mm.

4. 4. A surface protection film according to claim 1, wherein the urethane-based adhesive layer is attached to a glass plate, and after 24 hours at 23° C., the residual adhesion rate to the glass plate is 80% or more after peeling from the glass plate at a peel angle of 180° and a peel speed of 0.3 m / min.

5. An optical member having the surface protective film according to claim 1 attached thereto.

6. An electronic component having the surface protective film according to claim 1 attached thereto.

Citation Information

Patent Citations

  • Method and device for controlling flow of fluid

    JP1980001489A

  • Urethane-based pressure-sensitive adhesive agent and surface protective film using the same

    JP2014111701A

  • Surface protective film

    JP2016017109A

  • Surface protective film

    JP2016108442A

  • Adhesive and adhesive tape

    JP2016176068A